Optical film, polarizing plate, and image display device

By using specific skeleton compounds in the optical film, controlling their phase difference value and wavelength dispersion value under high temperature and light, the problem of unstable performance of the existing optical film is solved, and the performance stability and reliability of the optical film are improved.

CN119596434APending Publication Date: 2025-03-11SUMITOMO CHEM CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411242500.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2023-09-08
Filing Date
2024-09-05
Publication Date
2025-03-11

AI Technical Summary

Technical Problem

In the high temperature environment and light, the phase difference value and wavelength dispersion value of the existing optical film are prone to change, resulting in unstable performance.

Method used

An optical film containing a specific skeleton compound is used to ensure that the phase difference value and wavelength dispersion value of the optical film under high temperature and light remains stable by controlling the content and composition of the compound (A) and compound (B).

Benefits of technology

The optical film has stable performance under high temperature and light, avoiding changes in phase difference value and wavelength dispersion value, thereby improving the reliability and service life of the optical film.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119596434A_ABST
    Figure CN119596434A_ABST
Patent Text Reader

Abstract

The invention relates to an optical film, a polarizing plate, and an image display device. The present invention addresses the problem of providing an optical film in which the phase difference value does not easily change even when exposed to a high-temperature environment, and in which the wavelength dispersion value does not easily change even when exposed to light. [Solution] An optical film according to the present disclosure contains a compound (A) having a skeleton represented by general formula (A1) as a partial structure and a compound (B) having a skeleton represented by formula (B1) as a partial structure, the content of the compound (A) per unit volume being 1.5-20 kg / m3, and the content of the compound (B) per unit volume being 2.5-30 kg / m3. In formula (A1), R1 represents a hydrogen atom, a hydrocarbon group, or a carbonyl group. # imgabs0 #
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present disclosure relates to an optical film, a polarizing plate and an image display device. Background Art

[0002] Flat panel displays (FPDs) use components including optical films such as polarizing plates and phase difference plates. As such optical films, there are known optical films formed using a composition including a polymerizable liquid crystal compound, a photopolymerization initiator, and a solvent (for example, Patent Document 1).

[0003] Prior art literature

[0004] Patent Literature

[0005] Patent Document 1: Japanese Patent Application Publication No. 2012-214801 Summary of the invention

[0006] Problems to be solved by the invention

[0007] Conventional optical films have a problem that their retardation value changes when exposed to a high temperature environment. Conventional optical films also have a problem that their wavelength dispersion value changes when exposed to light.

[0008] The present disclosure provides an optical film whose phase difference value is not easily changed even when exposed to a high temperature environment and whose wavelength dispersion value is not easily changed even when exposed to light. In addition, the present disclosure provides a polarizing plate having such an optical film and an image display device having the same.

[0009] Means for solving problems

[0010] In order to solve the above-mentioned problems, the present disclosure provides the following optical films, polarizing plates, and image display devices.

[0011] [1] An optical film comprising a compound (A) having a skeleton represented by the following general formula (A1) as a partial structure, and a compound (B) having a skeleton represented by the following formula (B1) as a partial structure,

[0012] The content of compound (A) per unit volume is 1.5 kg / m 3 Above 20kg / m 3 the following,

[0013] The content of compound (B) per unit volume is 2.5 kg / m 3 Above 30kg / m 3 the following.

[0014] [Chemical formula 1]

[0015]

[0016] [In formula (A1), R 1 represents a hydrogen atom, a hydrocarbon group or a carbonyl group.]

[0017] [Chemical formula 2]

[0018]

[0019] [2] The optical film according to [1], which satisfies the following formulas (1) and (2).

[0020] 0.82≤Re(450) / Re(550)≤0.98 (1)

[0021] 100nm≤Re(550)≤160nm (2)

[0022] [Wherein, Re(450) represents the in-plane phase difference value for light with a wavelength of 450 nm, and Re(550) represents the in-plane phase difference value for light with a wavelength of 550 nm.]

[0023] [3] The optical film according to [1] or [2], wherein the thickness is 0.5 μm or more and 5 μm or less.

[0024] [4] The optical film according to any one of [1] to [3], comprising a cured product of a polymerizable liquid crystal compound.

[0025] [5] A polarizing plate comprising a polarizing film and the optical film according to any one of [1] to [4].

[0026] [6] An image display device comprising the polarizing plate described in [5].

[0027] Effects of the Invention

[0028] According to the present disclosure, an optical film can be provided, whose phase difference value is not easily changed even when exposed to a high temperature environment, and whose wavelength dispersion value is not easily changed even when exposed to light. In addition, according to the present disclosure, a polarizing plate having such an optical film and an image display device having the same can be provided. DETAILED DESCRIPTION

[0029] [Optical film]

[0030] The optical film involved in one embodiment is described below. The optical film involved in this embodiment (hereinafter, also referred to as "optical film") contains a compound (A) having a skeleton represented by the following general formula (A1) as a partial structure (hereinafter, also referred to as "compound (A)"), and a compound (B) having a skeleton represented by the following formula (B1) as a partial structure (hereinafter, also referred to as "compound (B)"), and the content of compound (A) per unit volume is 1.5 kg / m 3 Above 20kg / m 3 Below, the content of compound (B) per unit volume is 2.5 kg / m 3 Above 30kg / m 3 the following.

[0031] [Chemical formula 3]

[0032]

[0033] [In formula (A1), R 1 represents a hydrogen atom, a hydrocarbon group or a carbonyl group.]

[0034] [Chemical formula 4]

[0035]

[0036] The optical film combination contains compound (A) and compound (B), and the content of each is within the above numerical range. Thus, even when the optical film is exposed to a high temperature environment, the change in the phase difference value is suppressed, and even when exposed to light, the wavelength dispersion value is not easily changed.

[0037] The skeleton represented by the general formula (A1) is a skeleton composed of carbon atoms, nitrogen atoms and R 1 The skeleton represented by the above formula (B1) is a skeleton composed of carbon atoms and sulfur atoms possessed by the compound represented by the above formula (B1).

[0038] In R 1 In the case of a hydrocarbon group, the hydrocarbon group may or may not have a branch. The number of carbon atoms in the hydrocarbon group may be 1 or more, 5 or more, or 8 or more, and may be 20 or less, 16 or less, or 10 or less. Examples of the hydrocarbon group include alkyl, alkenyl, alkynyl, aryl, and aralkyl. One or more hydrogen atoms in the hydrocarbon group may be substituted with a substituent. Examples of such a substituent include a hydroxyl group.

[0039] In R 1 In the case of a carbonyl group, examples of the carbonyl group include a formyl group, an acetyl group, an ethylcarbonyl group, a butyryl group, a cyclohexylcarbonyl group, an allylcarbonyl group, a phenylcarbonyl group, and a methylphenylcarbonyl group.

[0040] From the perspective that the resulting optical film tends to have a phase difference value that is less likely to change even when exposed to a high temperature environment and that suppresses the generation of bright spot defects, the compound (A) contained in the optical film preferably has at least one of the substituents represented by the following general formulas (A11) to (A14).

[0041] [Chemical formula 5]

[0042]

[0043] In formulae (A11) to (A14), ※ represents a connecting bond.

[0044] In formula (A11), R 11 The number of carbon atoms in the hydrocarbon group may be, for example, 1 to 20. In formula (A11), n11 represents an integer of 1 to 5.

[0045] In formula (A12), R 12 The hydrocarbon group may have 1 to 20 carbon atoms, for example.

[0046] In formula (A13), R 13 The number of carbon atoms in the hydrocarbon group may be, for example, 1 to 20. In formula (A13), n13 represents an integer of 1 to 5.

[0047] In formula (A14), R 14 represents a hydrocarbon group having no fluorine atom or a hydrocarbon group having a fluorine atom. The number of carbon atoms in the hydrocarbon group may be, for example, 1 to 20. In formula (A14), n14 represents an integer of 1 to 5.

[0048] From the perspective that the obtained optical film has a tendency to have a retardation value that is less likely to change even when exposed to a high temperature environment and to suppress the generation of bright spot defects, the compound (A) contained in the optical film is preferably a compound having a group represented by any one of the following formulas (A21) to (A23), and more preferably a compound having a group represented by the following formula (A21). In formulas (A21) to (A23), ※ represents a connecting bond.

[0049] [Chemical formula 6]

[0050]

[0051] From the perspective that the resulting optical film tends to have a phase difference value that is less likely to change even when exposed to a high temperature environment and that suppresses the generation of bright spot defects, the compound (A) contained in the optical film is preferably a compound represented by the following formulas (A31) to (A37) and a compound derived from the compounds represented by the following formulas (A31) to (A33), and more preferably a compound represented by the following formula (A31) and a compound derived from the compound represented by the following formula (A31).

[0052] [Chemical formula 7]

[0053]

[0054] [Chemical formula 8]

[0055]

[0056] The CLogP of the compound (A) contained in the optical film is preferably 1 to 30, and more preferably 9 to 20, from the perspective of the tendency that the obtained optical film becomes an optical film whose phase difference value is less likely to change even when exposed to a high temperature environment and in which the generation of bright spot defects is suppressed. CLogP is a value for estimating the affinity of an organic compound for water and 1-octanol [P = (concentration of organic compound in 1-octanol phase) / (concentration of organic compound in water phase)], and can be calculated by a calculation program using the fragmentation value of atomic groups determined by the number of atoms constituting the compound and the type of chemical bond. In this specification, CLogP refers to a value calculated using ChemDraw ver. 18.2 of PerkinElmer.

[0057] The content of the compound (A) per unit volume of the optical film was 1.5 kg / m 3 The content is preferably 6 kg / m 2 because the resulting optical film tends to have a less change in retardation value even when exposed to a high temperature environment and to suppress the generation of bright spot defects. 3 The content of the compound (A) per unit volume of the optical film is 20 kg / m 3 The content is preferably 18 kg / m 2 because the resulting optical film tends to have a retardation value that is less likely to change even when exposed to a high temperature environment and to suppress the occurrence of bright spot defects. 3 the following.

[0058] From the perspective of the tendency of the optical film to be an optical film whose wavelength dispersion value and phase difference value are less likely to change even when exposed to light, the compound (B) contained in the optical film preferably has a substituent represented by the following general formula (B11). From the same perspective, the number of the substituents is preferably 1 or 2, more preferably 2.

[0059] [Chemical formula 9]

[0060]

[0061] In formula (B11), ※ represents a connecting bond.

[0062] In formula (B11), R 111 The hydrocarbon group may have 1 to 16 carbon atoms, for example.

[0063] From the perspective of the tendency of the optical film to become an optical film whose wavelength dispersion value and phase difference value are less likely to change even when exposed to light, the compound (B) contained in the optical film is preferably a compound having a group represented by any one of the following formulas (B21) and (B22), and from the perspective of the tendency of the optical film to become an optical film whose phase difference value is less likely to change even when exposed to light, it is more preferably a compound having a group represented by the following formula (B21). In formulas (B21) and (B22), ※ represents a connecting bond.

[0064] From the perspective of the tendency for the optical film to become an optical film in which the wavelength dispersion value and the phase difference value are less likely to change even when exposed to light, the compound (B) contained in the optical film is preferably a compound represented by the following formulae (B31) to (B36) and a compound derived from the compounds represented by the following formulae (B31) and (B32). From the perspective of the tendency for the optical film to become an optical film in which the phase difference value is less likely to change even when exposed to light, the compound (B) contained in the optical film is preferably a compound represented by the following formula (B31) and a compound derived from the compound represented by the following formula (B31).

[0065] [Chemical formula 10]

[0066]

[0067] The CLogP of the compound (B) contained in the optical film is preferably 4 to 9, more preferably 4 to 5, because the optical film tends to have a less change in wavelength dispersion value and phase difference value even when exposed to light.

[0068] The content of the compound (B) per unit volume of the optical film is 2.5 kg / m 3The content is preferably 3 kg / m 2 because the optical film tends to have a less change in wavelength dispersion value and phase difference value even when exposed to light. 3 The content of the compound (B) per unit volume of the optical film is 30 kg / m 3 From the viewpoint that there is a tendency for the optical film to have a less change in wavelength dispersion value and phase difference value even when the optical film is exposed to light, the content is preferably 29 kg / m 3 the following.

[0069] The optical film preferably contains at least one of a cured product and an uncured product of a polymerizable liquid crystal compound in addition to compound (A) and compound (B). The optical film may be a cured product of a polymerizable liquid crystal composition containing a polymerizable liquid crystal compound, compound (A) and compound (B). Compound (A) and compound (B) may have functions such as a leveling agent, an antioxidant, a polymerization initiator and a colorant in the polymerizable liquid crystal composition.

[0070] The content of the cured product of the polymerizable liquid crystal compound may be 70% by mass or more, 80% by mass or more, 90% by mass or more, or 95% by mass or more based on the total amount of the optical film.

[0071] In the present specification, the polymerizable liquid crystal compound refers to a liquid crystal compound having a polymerizable group, particularly a photopolymerizable group. As the polymerizable liquid crystal compound, for example, a polymerizable liquid crystal compound conventionally known in the field of retardation films can be used.

[0072] The so-called polymerizable group refers to a group that can participate in the polymerization reaction. The so-called photopolymerizable group refers to a group that can participate in the polymerization reaction using reactive species such as active free radicals, acids, etc. generated by a photopolymerization initiator as a polymerizable group. As a photopolymerizable group, for example, vinyl, vinyloxy, 1-chlorovinyl, isopropenyl, 4-vinylphenyl, acryloyloxy, methacryloyloxy, oxacyclopropyl and oxetane can be cited. Among them, acryloyloxy, methacryloyloxy, vinyloxy, oxacyclopropyl and oxetane are preferred, and acryloyloxy is more preferred. The liquid crystal properties displayed by the polymerizable liquid crystal compound can be thermotropic liquid crystal or lyotropic liquid crystal. From the perspective of being able to perform precise film thickness control, it is preferably a thermotropic liquid crystal. In addition, as a phase-ordered structure in a thermotropic liquid crystal, it can be a nematic liquid crystal or a smectic liquid crystal. The polymerizable liquid crystal compound can be used alone or in combination of two or more.

[0073] As the polymerizable liquid crystal compound, a compound having the following characteristics (1) to (4) is preferred.

[0074] (1) A compound that can form a nematic phase or a smectic phase.

[0075] (2) The polymerizable liquid crystal compound has π electrons in the long axis direction (a).

[0076] (3) It has π electrons in a direction intersecting the long axis direction (a) (intersecting direction (b)).

[0077] (4) The π electron density in the long axis direction (a) of the polymerizable liquid crystal compound is defined by the following formula (i), where the total number of π electrons present in the long axis direction (a) is N(πa) and the total molecular weight present in the long axis direction is N(Aa):

[0078] D(πa)=N(πa) / N(Aa)(i), and,

[0079] The total number of π electrons present in the cross direction (b) is denoted as N(πb), and the total number of molecular weights present in the cross direction (b) is denoted as N(Ab), and the π electron density in the cross direction (b) of the polymerizable liquid crystal compound is defined by the following formula (ii):

[0080] D(πb)=N(πb) / N(Ab) (ii)

[0081] The relationship of existence (iii) is:

[0082] 0≤〔D(πa) / D(πb)〕<1 (iii)

[0083] [That is, the π electron density in the intersecting direction (b) is greater than that in the long axis direction (a).] In addition, the polymerizable liquid crystal compound having π electrons in the long axis and in the direction intersecting therewith as described above forms, for example, a T-shaped structure.

[0084] The polymerizable liquid crystal compound is preferably a compound capable of forming a nematic phase.

[0085] In the above-mentioned features (1) to (4), the major axis direction (a) and the number of π electrons N are defined as follows.

[0086] For example, in the case of a compound having a rod-like structure, the major axis direction (a) is the major axis direction of the rod.

[0087] The number of π electrons N(πa) present in the major axis direction (a) does not include π electrons that disappear due to the polymerization reaction.

[0088] The number of π electrons N(πa) existing in the long axis direction (a) includes the total number of π electrons on the long axis and π electrons conjugated thereto, for example, the number of π electrons existing in the ring existing in the long axis direction (a) and satisfying Huckel's rule.

[0089] The number of π electrons N(πb) present in the crossing direction (b) does not include π electrons that disappear due to the polymerization reaction.

[0090] The polymerizable liquid crystal compound satisfying the above characteristics has a mesostructure in the long-axis direction and exhibits a liquid crystal phase (nematic phase, smectic phase) by virtue of the mesostructure.

[0091] The polymerizable liquid crystal compound satisfying the above (1) to (4) can be coated on the photo-alignment film described later and heated to a temperature above the phase transition temperature to form a nematic phase or a smectic phase. In the nematic phase or smectic phase formed by the orientation of the polymerizable liquid crystal compound, for example, the polymerizable liquid crystal compound is oriented in a manner that the long axis directions are parallel to each other, and the long axis direction becomes the orientation direction of the nematic phase. If such a polymerizable liquid crystal compound is made into a film and polymerized in a nematic phase or a smectic phase, a polymer film formed by a polymer obtained by polymerization in a state oriented along the long axis direction (a) can be formed. The polymer film absorbs ultraviolet rays using π electrons in the long axis direction (a) and π electrons in the cross direction (b).

[0092] Here, the absorption maximum wavelength of ultraviolet light absorbed by the π electrons in the cross direction (b) is set to λbmax. λbmax is usually 300nm to 400nm. The density of π electrons satisfies the above formula (iii), and the π electron density in the cross direction (b) is greater than the π electron density in the long axis direction (a). Therefore, the absorption of linearly polarized ultraviolet light (wavelength λbmax) having a vibration plane in the cross direction (b) is greater than the absorption of linearly polarized ultraviolet light (wavelength λbmax) having a vibration plane in the long axis direction (a) The polymer film. The ratio (absorbance of linearly polarized ultraviolet light in the cross direction (b) / absorbance in the long axis direction (a)) is, for example, greater than 1.0, preferably greater than 1.2 and less than 30, for example, less than 10.

[0093] The polymerizable liquid crystal compound having the above-mentioned characteristics is usually a compound that shows reverse wavelength dispersion. Specifically, for example, a compound represented by the following formula (X) is mentioned.

[0094] [Chemical formula 11]

[0095]

[0096] In formula (X), Ar represents a divalent aromatic group which may have a substituent. Here, the so-called aromatic group refers to a group containing an aromatic ring having a π electron number of [4n+2] according to the Huckel rule. Here, n represents an integer. In the case where the ring structure is formed in a manner including heteroatoms such as -N= and -S-, the case where the non-covalent electron pairs on these heteroatoms satisfy the Huckel rule and have aromaticity is also included. It is preferred that at least one of a nitrogen atom, an oxygen atom and a sulfur atom is included in the aromatic group. The aromatic ring contained in Ar may be one or more. In the case where the aromatic ring contained in Ar is two or more, the two or more aromatic rings may be bonded to each other through a single bond, -CO-O-, -O- and other divalent bonding groups.

[0097] G 1 and G 2 Each independently represents a divalent aromatic group or a divalent alicyclic hydrocarbon group. Here, the hydrogen atoms contained in the divalent aromatic group or the divalent alicyclic hydrocarbon group may be substituted by a halogen atom, an alkyl group having 1 to 4 carbon atoms, a fluoroalkyl group having 1 to 4 carbon atoms, an alkoxy group having 1 to 4 carbon atoms, a cyano group or a nitro group, and the carbon atoms constituting the divalent aromatic group or the divalent alicyclic hydrocarbon group may be substituted by an oxygen atom, a sulfur atom or a nitrogen atom.

[0098] G 1 and G 2 Each independently preferably is a 1,4-phenylenediyl group which may be substituted with at least one substituent selected from the group consisting of a halogen atom and an alkyl group having 1 to 4 carbon atoms, or a 1,4-cyclohexanediyl group which may be substituted with at least one substituent selected from the group consisting of a halogen atom and an alkyl group having 1 to 4 carbon atoms, more preferably a 1,4-phenylenediyl group substituted with a methyl group, an unsubstituted 1,4-phenylenediyl group or an unsubstituted 1,4-trans-cyclohexanediyl group, and further preferably an unsubstituted 1,4-phenylenediyl group or an unsubstituted 1,4-trans-cyclohexanediyl group.

[0099] In addition, it is preferred that there are a plurality of G 1 and G 2 At least one of them is a divalent alicyclic hydrocarbon group, and more preferably 1 or L 2 Bonded G 1 and G 2 At least one of them is a divalent alicyclic hydrocarbon group.

[0100] L 1 , L 2 , B 1 and B 2 Each is independently a single bond or a divalent linking group.

[0101] L1 and L 2 Each of them is independently preferably a single bond, an alkylene group having 1 to 4 carbon atoms, -O-, -S-, -R a1 OR a2 -、-R a3 COOR a4 -、-R a5 OCOR a6 -、R a7 OC=OOR a8 -、-N=N-、-CR c =CR d -or-C≡C-. Here, R a1 ~R a8 Each independently represents a single bond or an alkylene group having 1 to 4 carbon atoms, and R c and R d represents an alkyl group having 1 to 4 carbon atoms or a hydrogen atom. 1 and L 2 Each independently is more preferably a single bond, -OR a2-1 -、-CH 2 -、-CH 2 CH 2 -、-COOR a4-1 -OCOR a6-1 -. Here, R a2-1 , R a4-1 and Ra 6-1 Each independently represents a single bond, -CH 2 - and - CH 2 CH 2 -Any one of L 1 and L 2 Each of them is independently more preferably a single bond, -O-, -CH 2 CH 2 -、-COO-、-COOCH 2 CH 2 -or OCO-.

[0102] B 1 and B 2 Each of them is independently preferably a single bond, an alkylene group having 1 to 4 carbon atoms, -O-, -S-, -R a9 OR a10 -、-R a11 COOR a12 -、-R a13 OCOR a14 - or R a15 OC=OOR a16 -. R a9 ~R a16 Each independently represents a single bond or an alkylene group having 1 to 4 carbon atoms.1 and B 2 Each independently is more preferably a single bond, -OR a10-1 -、-CH 2 -、-CH 2 CH 2 -、-COOR a12-1 -OCOR a14-1 -. Here, R a10-1 , R a12-1 and R a14-1 Each independently represents a single bond, -CH 2 - and - CH 2 CH 2 -Any one of B. 1 and B 2 Each of them is independently more preferably a single bond, -O-, -CH 2 CH 2 -、-COO-、-COOCH 2 CH 2 -, -OCO- or OCOCH 2 CH 2 -.

[0103] k and l each independently represent an integer of 0 to 3 and satisfy the relationship 1≤k+1. Here, when 2≤k+1, there are a plurality of B 1 , B 2 , G 1 and G 2 Each may be the same as or different from each other.

[0104] From the viewpoint of exhibiting reverse wavelength dispersion, k and l are preferably in the range of 2≤k+l≤6, preferably k+l=4, and more preferably k=2 and l=2. k=2 and l=2 are preferred because a symmetrical structure is obtained.

[0105] E 1 and E 2 Each independently represents an alkanediyl group having 1 to 17 carbon atoms. 1 and E 2 More preferably, it is an alkanediyl group having 4 to 12 carbon atoms. In addition, the hydrogen atoms contained in the alkanediyl group may be substituted with halogen atoms, and the -CH 2 - can be -O-, -S-, -SiH 2 - or -C(=O)- substituted.

[0106] P 1 and P 2 Each independently represents a polymerizable group or a hydrogen atom, and at least one of them is a polymerizable group.

[0107] As P1 or P 2 The polymerizable group represented by , includes epoxy, vinyl, vinyloxy, 1-chlorovinyl, isopropenyl, 4-vinylphenyl, acryloyloxy, methacryloyloxy, oxirane, and oxetanyl, etc. Among them, acryloyloxy, methacryloyloxy, vinyloxy, oxirane, and oxetanyl are preferred, and acryloyloxy is more preferred.

[0108] Ar preferably has at least one selected from the group consisting of an aromatic hydrocarbon ring that may have a substituent, an aromatic heterocycle that may have a substituent, and an electron-withdrawing group. As the aromatic hydrocarbon ring, for example, benzene ring, naphthalene ring, anthracene ring, etc. can be cited, preferably benzene ring, naphthalene ring. As the aromatic heterocycle, furan ring, benzofuran ring, pyrrole ring, indole ring, thiophene ring, benzothiophene ring, pyridine ring, pyrazine ring, pyrimidine ring, triazole ring, triazine ring, pyrroline ring, imidazole ring, pyrazole ring, thiazole ring, benzothiazole ring, thienothiazole ring, oxazole ring, benzoxazole ring, and phenanthroline ring, etc. can be cited. Among them, preferably there is thiazole ring, benzothiazole ring or benzofuran ring, further preferably there is benzothiazolyl. In addition, in the case of including a nitrogen atom in Ar, the nitrogen atom preferably has π electrons.

[0109] In formula (X), the total number Nπ of π electrons contained in the divalent aromatic group represented by Ar is preferably 8 or more, more preferably 10 or more, further preferably 14 or more, and particularly preferably 16 or more. It is preferably 30 or less, more preferably 26 or less, and further preferably 24 or less.

[0110] Examples of the aromatic group represented by Ar include the following groups.

[0111] [Chemical formula 12]

[0112]

[0113] In formula (Ar-1) to formula (Ar-23), the symbol * represents a connecting bond, and Z 0 , Z 1 and Z 2 Each independently represents a hydrogen atom, a halogen atom, an alkyl group having 1 to 12 carbon atoms, a cyano group, a nitro group, an alkylsulfinyl group having 1 to 12 carbon atoms, an alkylsulfonyl group having 1 to 12 carbon atoms, a carboxyl group, a fluoroalkyl group having 1 to 12 carbon atoms, an alkoxy group having 1 to 12 carbon atoms, an alkylthio group having 1 to 12 carbon atoms, an N-alkylamino group having 1 to 12 carbon atoms, an N,N-dialkylamino group having 2 to 12 carbon atoms, an N-alkylsulfamoyl group having 1 to 12 carbon atoms, or an N,N-dialkylsulfamoyl group having 2 to 12 carbon atoms. 0 , Z 1 and Z2 A polymerizable group may also be contained.

[0114] Q 1 and Q 2 Each independently represents -CR 21 R 22 -、-S-、-NH-、-NR 21 -, -CO- or -O-, R 21 and R 22 Each independently represents a hydrogen atom or an alkyl group having 1 to 4 carbon atoms.

[0115] Q 1 and Q 2 Preferred are -NH-, -S-, -NR 21 - and -O-. R 21 It is preferably a hydrogen atom. 1 and Q 2 More preferred are -S-, -O- and -NH-.

[0116] J 1 and J 2 Each independently represents a carbon atom or a nitrogen atom.

[0117] Y 1 , Y 2 and Y 3 Each independently represents an aromatic hydrocarbon group or an aromatic heterocyclic group which may be substituted.

[0118] W 1 and W 2 Each independently represents a hydrogen atom, a cyano group, a methyl group or a halogen atom, and m represents an integer of 0-6.

[0119] As Y 1 , Y 2 and Y 3 The aromatic hydrocarbon group in the group includes aromatic hydrocarbon groups having 6 to 20 carbon atoms such as phenyl, naphthyl, anthracenyl, phenanthryl and biphenyl, preferably phenyl and naphthyl, more preferably phenyl. The aromatic heterocyclic group includes aromatic heterocyclic groups having 4 to 20 carbon atoms and containing at least one hetero atom such as a nitrogen atom, an oxygen atom or a sulfur atom such as furanyl, pyrrolyl, thienyl, pyridyl, thiazolyl and benzothiazolyl, preferably furanyl, thienyl, pyridyl, thiazolyl and benzothiazolyl.

[0120] Y 1 , Y 2 and Y 3Each independently may be a substituted polycyclic aromatic hydrocarbon group or a polycyclic aromatic heterocyclic group. A polycyclic aromatic hydrocarbon group refers to a condensed polycyclic aromatic hydrocarbon group or a group derived from an aromatic ring collection. A polycyclic aromatic heterocyclic group refers to a condensed polycyclic aromatic heterocyclic group or a group derived from an aromatic ring collection.

[0121] Z 0 , Z 1 and Z 2 Each of Z is independently preferably a hydrogen atom, a halogen atom, an alkyl group having 1 to 12 carbon atoms, a cyano group, a nitro group, and an alkoxy group having 1 to 12 carbon atoms. 0 More preferably, Z is a hydrogen atom, an alkyl group having 1 to 12 carbon atoms, or a cyano group. 1 and Z 2 More preferred are a hydrogen atom, a fluorine atom, a chlorine atom, a methyl group and a cyano group. 0 , Z 1 and Z 2 A polymerizable group may also be contained.

[0122] Among formulae (Ar-1) to (Ar-23), formulae (Ar-6) and (Ar-7) are preferred from the viewpoint of molecular stability.

[0123] In the formulas (Ar-16) to (Ar-23), Y 1 The nitrogen atom and Z to which it can be bonded 0 Together, they form an aromatic heterocyclic group. Examples of the aromatic heterocyclic group include the rings described above as aromatic heterocyclic rings that Ar may have, such as a pyrrole ring, an imidazole ring, a pyrroline ring, a pyridine ring, a pyrazine ring, a pyrimidine ring, an indole ring, a quinoline ring, an isoquinoline ring, a purine ring, and a pyrrolidine ring. The aromatic heterocyclic group may have a substituent. In addition, Y 1 It can also be bonded to the nitrogen atom and Z 0 Together, they are the above-mentioned optionally substituted polycyclic aromatic hydrocarbon groups or polycyclic aromatic heterocyclic groups. Examples thereof include a benzofuran ring, a benzothiazole ring, and a benzoxazole ring.

[0124] Relative to 100 parts by mass of the solid content of the polymerizable liquid crystal composition, the content of the polymerizable liquid crystal compound in the polymerizable liquid crystal composition is, for example, 70 to 99.5 parts by mass, preferably 80 to 99 parts by mass, more preferably 85 to 98 parts by mass, and further preferably 90 to 95 parts by mass. If the content of the polymerizable liquid crystal compound is within the above range, it is advantageous from the perspective of the orientation of the obtained liquid crystal cured film. It should be noted that in this specification, the so-called solid content of the polymerizable liquid crystal composition refers to all components after removing volatile components such as organic solvents from the polymerizable liquid crystal composition.

[0125] The polymerizable liquid crystal composition includes compound (A). From the perspective of the tendency of the obtained optical film to be an optical film in which the phase difference value is less likely to change even when exposed to a high temperature environment and the generation of bright spot defects is suppressed, the content of the compound (A) in the polymerizable liquid crystal composition is, for example, 1 to 20 parts by mass, preferably 3 to 12 parts by mass, and more preferably 5 to 10 parts by mass, relative to 100 parts by mass of the solid content of the polymerizable liquid crystal composition.

[0126] The polymerizable liquid crystal composition includes a compound (B). From the perspective of the tendency of the optical film to be an optical film whose wavelength dispersion value and phase difference value are less likely to change even when exposed to light, the content of the compound (B) in the polymerizable liquid crystal composition is, for example, 1 to 20 parts by mass, preferably 3 to 12 parts by mass, and more preferably 5 to 10 parts by mass, relative to 100 parts by mass of the solid content of the polymerizable liquid crystal composition.

[0127] The polymerizable liquid crystal composition may contain additives such as a solvent, a photopolymerization initiator, a leveling agent, an antioxidant, and a photosensitizer in addition to the polymerizable liquid crystal compound, compound (A) and compound (B). These components may be used alone or in combination of two or more.

[0128] The polymerizable liquid crystal composition is usually applied to a substrate in a state dissolved in a solvent, and therefore preferably contains a solvent. The solvent is preferably a solvent that can dissolve the polymerizable liquid crystal compound and is preferably a solvent that is inactive to the polymerization reaction of the polymerizable liquid crystal compound. Examples of the solvent include alcohol solvents such as water, methanol, ethanol, ethylene glycol, isopropanol, propylene glycol, ethylene glycol methyl ether, ethylene glycol butyl ether, 1-methoxy-2-propanol, 2-butoxyethanol, and propylene glycol monomethyl ether; ester solvents such as ethyl acetate, butyl acetate, ethylene glycol methyl ether acetate, γ-butyrolactone, propylene glycol methyl ether acetate, and ethyl lactate; ketone solvents such as acetone, methyl ethyl ketone, cyclopentanone, cyclohexanone, 2-heptanone, and methyl isobutyl ketone; aliphatic hydrocarbon solvents such as pentane, hexane, and heptane; alicyclic hydrocarbon solvents such as ethylcyclohexane; aromatic hydrocarbon solvents such as toluene and xylene; nitrile solvents such as acetonitrile; ether solvents such as tetrahydrofuran and dimethoxyethane; chlorinated solvents such as chloroform and chlorobenzene; amide solvents such as dimethylacetamide, dimethylformamide, N-methyl-2-pyrrolidone (NMP), and 1,3-dimethyl-2-imidazolidinone; and the like. These solvents may be used alone or in combination of two or more thereof. Among them, alcohol solvents, ester solvents, ketone solvents, chlorine-containing solvents, amide solvents, and aromatic hydrocarbon solvents are preferred.

[0129] Relative to 100 parts by mass of polymerizable liquid crystal composition, the content of the solvent in the polymerizable liquid crystal composition is preferably 50 to 98 parts by mass, more preferably 70 to 95 parts by weight. Therefore, the solid component preferably accounts for 2 to 50 parts by mass in 100 parts by mass of the polymerizable liquid crystal composition. If the solid component is less than 50 parts by mass, the viscosity of the polymerizable liquid crystal composition decreases, so the thickness of the film becomes roughly uniform, and there is a tendency that it is not easy to produce unevenness. The above-mentioned solid component can be appropriately determined considering the thickness of the liquid crystal cured film to be manufactured.

[0130] A polymerization initiator is a compound that generates reactive species by the action of heat or light and can initiate a polymerization reaction of a polymerizable liquid crystal compound or the like. As reactive species, there can be mentioned active species such as free radicals or cations or anions. Among them, from the viewpoint of easy control of the reaction, a photopolymerization initiator that generates free radicals by light irradiation is preferred.

[0131] Examples of the photopolymerization initiator include benzoin compounds, benzophenone compounds, benzyl ketal compounds, oxime compounds, α-hydroxyketone compounds, α-aminoketone compounds, triazine compounds, iodonium salts, and sulfonium salts.

[0132] The content of the photopolymerization initiator is, for example, 0.1 to 30 parts by mass, preferably 1 to 20 parts by mass, and more preferably 1 to 15 parts by mass relative to 100 parts by mass of the polymerizable liquid crystal compound. Within the above range, the reaction of the polymerizable group proceeds sufficiently and the alignment of the polymerizable liquid crystal compound is less likely to be disturbed.

[0133] The so-called leveling agent is an additive that has the function of adjusting the fluidity of the polymerizable liquid crystal composition and making the coating film obtained by applying the composition flatter. For example, silicone-based, polyacrylate-based and perfluoroalkyl-based leveling agents can be cited. As the leveling agent, commercially available products can be used, specifically, DC3PA, SH7PA, DC11PA, SH28PA, SH29PA, SH30PA, ST80PA, ST86PA, SH8400, SH8700, FZ2123 (all of the above are made by Toray Dow Corning Co., Ltd.), KP321, KP323, KP324, KP326, KP340, KP341, X22-16 1A, KF6001 (all manufactured by Shin-Etsu Chemical Co., Ltd.), TSF400, TSF401, TSF410, TSF4300, TSF4440, TSF4445, TSF-4446, TSF4452, TSF4460 (all manufactured by Momentive Materials Japan Co., Ltd.), fluorinert (Flurinert) (registered trademark) FC-72, fluorinert FC-40, fluorinert FC-43, fluorinert FC-3283 (all manufactured by Sumitomo 3M Co., Ltd.), MEGAFACE (registered trademark) R-08, MEGAFACE R-30, MEGAF ACE R-90, MEGAFACE F-410, MEGAFACE F-411, MEGAFACE F-443, MEGAFACE F-445, MEGAFACE F-470, MEGAFACE F-477, MEGAFACE F-479, MEGAFACE F-482, MEGAFACE F-483 (all manufactured by DIC Corporation), EFTOP (trade name) EF301, EFTOP EF 303, EFTOP EF351, EFTOP EF352 (all manufactured by Mitsubishi Materials Electronic Chemicals Co., Ltd.), Surflon (registered trademark) S-381, Surflon S-382, Surflon S-383, Surflon S-393, Surflon SC-101, Surflon SC-105, KH-40, SA-100 (all manufactured by AGC Seimi Chemical Co., Ltd.), trade name E1830, trade name E5844 (manufactured by Daikin Fine Chemicals Laboratories), BM-1000, BM-1100, BYK-352, BYK-353 and BYK-361N (all trade names: manufactured by BM Chemie), etc. The leveling agent may be used alone or in combination of two or more.

[0134] The content of the leveling agent is preferably 0.01 to 5 parts by mass, more preferably 0.05 to 3 parts by mass, relative to 100 parts by mass of the polymerizable liquid crystal compound. When the content of the leveling agent is within the above range, the resulting liquid crystal cured film tends to be smoother, which is preferred.

[0135] By combining an antioxidant, the polymerization reaction of the polymerizable liquid crystal compound can be controlled. As an antioxidant, it can be a primary antioxidant selected from phenolic antioxidants, amine antioxidants, quinone antioxidants, and nitroso antioxidants, or it can be a secondary antioxidant selected from phosphorus antioxidants and sulfur antioxidants. In order to polymerize the polymerizable liquid crystal compound without disturbing the orientation of the polymerizable liquid crystal compound, the content of the antioxidant is, for example, 0.01 to 10 parts by mass, preferably 0.1 to 5 parts by mass, and more preferably 0.1 to 3 parts by mass, relative to 100 parts by mass of the polymerizable liquid crystal compound. The antioxidant can be used alone or in combination of two or more.

[0136] In addition, by using a photosensitizer, the photopolymerization initiator can be made highly sensitive. As the photosensitizer, for example, xanthone such as xanthone and thioxanthone; anthracene and anthracene having a substituent such as an alkyl ether; phenothiazine; rubrene. The photosensitizer can be used alone or in combination of two or more. The content of the photosensitizer is, for example, 0.01 to 10 parts by mass, preferably 0.05 to 5 parts by mass, and more preferably 0.1 to 3 parts by mass relative to 100 parts by mass of the polymerizable liquid crystal compound.

[0137] The polymerizable liquid crystal composition can be obtained by stirring the compound (A), the compound (B), the polymerizable liquid crystal compound, and components other than the polymerizable liquid crystal compound such as a solvent at a predetermined temperature.

[0138] The optical film can be made, for example, as described below. That is, first, a coating of a polymerizable liquid crystal composition is formed. The polymerizable liquid crystal compound is oriented in a horizontal direction relative to the plane of the coating. The polymerizable liquid crystal composition is cured while maintaining the horizontal orientation state of the polymerizable liquid crystal compound. The optical film is thus made. As a method for aligning the polymerizable liquid crystal compound in a horizontal direction, for example, a method of applying a polymerizable liquid crystal composition containing a rod-shaped polymerizable liquid crystal compound that is easily oriented horizontally to a horizontal orientation film described later can be cited.

[0139] The optical film preferably satisfies the following formulae (1) and (2). When the optical film satisfies these formulae, when a circularly polarizing plate including the optical film is used in an organic EL display device, the reflected hue is improved and coloration tends to be less likely to occur during black display.

[0140] 0.82≤Re(450) / Re(550)≤0.98 (1)

[0141] 100nm≤Re(550)≤160nm (2)

[0142] [Wherein, Re(450) represents the in-plane phase difference value for light with a wavelength of 450 nm, and Re(550) represents the in-plane phase difference value for light with a wavelength of 550 nm.]

[0143] From the same viewpoint, Re(450) / Re(550) is preferably 0.70 or more, more preferably 0.78 or more, and is preferably 0.95 or less, more preferably 0.92 or less.

[0144] From the same viewpoint, Re(550) is preferably 130 nm or more and preferably 150 nm or less.

[0145] Re(450) may be greater than or equal to 110 nm and less than or equal to 130 nm.

[0146] Re(630) may be greater than or equal to 135 nm and less than or equal to 155 nm.

[0147] Re(630) / Re(550) may be 0.95 or more and 1.05 or less. Re(630) represents an in-plane phase difference value for light of a wavelength of 630 nm.

[0148] The in-plane phase difference value is determined by the following formula (3). Therefore, the in-plane phase difference value (Re (λ): the in-plane phase difference value of the optical film at wavelength λ (nm)) can be adjusted by changing the three-dimensional refractive index and thickness d. The three-dimensional refractive index depends on the molecular structure and orientation state of the polymerizable liquid crystal compound.

[0149] Re(λ)=(nx(λ)-ny(λ) )×d (3)

[0150] [Wherein, nx(λ) represents the principal refractive index at a wavelength λ in the plane of the optical film, ny(λ) represents the refractive index at a wavelength λ in the same plane as nx and in a direction orthogonal to the direction of nx, and d represents the thickness of the optical film.]

[0151] The thickness of the optical film is preferably 0.5 to 5.0 μm, more preferably 0.8 to 4 μm, and further preferably 1.0 to 3.5 μm.

[0152] [Laminated body]

[0153] The laminated body according to the present embodiment (hereinafter, also simply referred to as a "laminated body") comprises the optical film according to the above-mentioned embodiment and a horizontal alignment film. The optical film can also be said to be a horizontal alignment liquid crystal cured film in the laminated body.

[0154] (Horizontal Alignment Film)

[0155] The horizontal alignment film has an alignment control force that aligns the polymerizable liquid crystal compound in the horizontal direction relative to the film plane of the liquid crystal cured film. The alignment control force can be arbitrarily adjusted by the type of alignment film, surface state, rubbing conditions, etc., and when the alignment film is formed of a photo-alignable polymer, it can be arbitrarily adjusted by polarized light irradiation conditions, etc.

[0156] As a horizontal alignment film, it is preferred to have solvent resistance that does not dissolve due to the coating of the polymerizable liquid crystal composition, and to have heat resistance in the heat treatment for the removal of the solvent and the orientation of the polymerizable liquid crystal compound described later. As a horizontal alignment film, a rubbing alignment film, a photoalignment film, and a groove alignment film having a concave-convex pattern and a plurality of grooves on the surface can be cited. From the perspective of the accuracy and quality of the orientation angle, a photoalignment film is preferably used.

[0157] The rubbed oriented film can be prepared, for example, as described below. That is, a composition comprising an oriented polymer and a solvent (hereinafter, also referred to as an "oriented polymer composition") is prepared. The oriented polymer composition is applied to the surface of a substrate, and the solvent is removed to obtain a coating film. The coating film is rubbed to impart an orientation control force. Thus, a rubbed oriented film can be obtained. As a solvent, for example, the same solvent as that which can be contained in a polymerizable liquid crystal composition can be cited.

[0158] As the oriented polymer, for example, polyamides having amide bonds in the molecule, gelatins, polyimides having imide bonds in the molecule and polyamic acid as their hydrolyzates, polyvinyl alcohol, alkyl-modified polyvinyl alcohol, polyacrylamide, polyoxazole, polyethyleneimine, polystyrene, polyvinyl pyrrolidone, polyacrylic acid and polyacrylates can be cited. Among them, polyvinyl alcohol is preferred. The oriented polymer can be used alone or in combination of two or more.

[0159] The concentration of the oriented polymer in the oriented polymer composition may be within a range in which the oriented polymer material can be completely dissolved in the solvent, and is preferably 0.1 to 20%, more preferably 0.1 to 10%, based on the solid content of the solution.

[0160] As the oriented polymer composition, a commercially available oriented film material may be used as it is. Examples of commercially available oriented film materials include SUNEVER (registered trademark, manufactured by Nissan Chemical Industries, Ltd.) and Optomer (registered trademark, manufactured by JSR Corporation).

[0161] The photo-alignment film can be prepared, for example, as described below. That is, a composition comprising at least one of a polymer and a monomer having a photoreactive group and a solvent (hereinafter also referred to as a "photo-alignment film-forming composition") is prepared. The photo-alignment film-forming composition is applied to the surface of the substrate, and the solvent is removed to obtain a coating film. Polarized light is irradiated to the coating film. Thus, a photo-alignment film can be obtained.) As far as the photo-alignment film is concerned, by selecting the polarization direction of the irradiated polarized light, the direction of the orientation control force can be arbitrarily controlled, which is also advantageous from this aspect.

[0162] The so-called photoreactive group refers to a group that generates liquid crystal orientation ability by light irradiation. Specifically, groups that participate in the photoreaction of the orientation induction or isomerization reaction, dimerization reaction, photocrosslinking reaction or photodecomposition reaction of molecules that occur by light irradiation, which become the source of liquid crystal orientation ability, can be cited. Among them, the group participating in the dimerization reaction or the photocrosslinking reaction is preferred from the aspect of excellent orientation. As a photoreactive group, it is preferably a group having an unsaturated bond, especially a double bond, and it is particularly preferred to have at least one group selected from the group consisting of a carbon-carbon double bond (C=C bond), a carbon-nitrogen double bond (C=N bond), a nitrogen-nitrogen double bond (N=N bond) and a carbon-oxygen double bond (C=O bond).

[0163] As photoreactive groups having C=C bonds, vinyl, polyene, stilbene, stilbazole, stilbazolium, chalcone, and cinnamoyl groups can be cited. As photoreactive groups having C=N bonds, groups having structures such as aromatic Schiff bases and aromatic hydrazones can be cited. As photoreactive groups having N=N bonds, azophenyl, azonaphthyl, aromatic heterocyclic azo, bisazo, formazan, and groups having an oxidized azobenzene structure can be cited. As photoreactive groups having C=O bonds, benzophenone, coumarin, anthraquinone, and maleimide groups can be cited. These groups can have substituents such as alkyl, alkoxy, aryl, allyloxy, cyano, alkoxycarbonyl, hydroxyl, sulfonic acid, and halogenated alkyl.

[0164] The photoreactive group is preferably a photoreactive group that participates in the photodimerization reaction, and is preferably a cinnamoyl group and a chalcone group from the viewpoint that the amount of polarized light irradiation required for photo-alignment is small and a photo-alignment film with excellent thermal stability and temporal stability is easily obtained. As a polymer having a photoreactive group that forms a horizontal alignment film, a polymer having a cinnamoyl group such as a cinnamic acid structure at the terminal of the polymer side chain is particularly preferred, because when the horizontal alignment liquid crystal cured film is formed by a polymerizable liquid crystal compound having a (meth)acryloyloxy group as a polymerizable group, the adhesion with the horizontal alignment liquid crystal cured film can be further improved.

[0165] Examples of the solvent contained in the photo-alignment film-forming composition include the same solvents as those that can be contained in the polymerizable liquid crystal composition. The solvent can be appropriately selected according to the solubility of the polymer or monomer having a photoreactive group.

[0166] The content of the polymer or monomer having a photoreactive group in the composition for forming a photo-alignment film can be appropriately adjusted according to the type of polymer or monomer and the thickness of the target photo-alignment film. Relative to the mass of the composition for forming a photo-alignment film, the content is preferably set to at least 0.2% by mass, more preferably in the range of 0.3 to 10% by mass. In addition, from the aspect of easy manufacture and the aspect of improving the adhesion with the horizontally aligned liquid crystal cured film when the horizontally aligned liquid crystal cured film is formed by a polymerizable liquid crystal compound having a (meth) acryloyloxy group as a polymerizable group, the polymer forming the photo-alignment film is preferably a (meth) acrylic polymer. Within the range that does not significantly damage the characteristics of the photo-alignment film, the composition for forming a photo-alignment film may also include polymer materials such as polyvinyl alcohol and polyimide, and photosensitizers.

[0167] The groove oriented film is a film having a concavo-convex pattern or a plurality of grooves (grooves) on the film surface. When a polymerizable liquid crystal compound is applied to a film having a plurality of linear grooves arranged at equal intervals, the liquid crystal molecules are oriented in the direction along the grooves.

[0168] The thickness of the alignment film (alignment film or photo-alignment film containing an alignment polymer) is, for example, 10 to 10000 nm, preferably 10 to 1000 nm, more preferably 10 to 500 nm or less, further preferably 10 to 300 nm, particularly preferably 50 to 250 nm.

[0169] (cured resin layer)

[0170] The laminate may include a cured resin layer. From the viewpoint of reducing the thickness of the laminate, the thickness of the cured resin layer is 0.1 to 10 μm, preferably 0.5 to 5 μm.

[0171] As the cured resin layer, for example, films of cycloolefin polymer (COP), polyethylene terephthalate (PET) and cellulose triacetate (TAC) etc. which can also be used as substrates described later and cured resin layer-forming compositions containing polymerizable monomers can be cited, but from the viewpoint of thin filmization, the cured resin layer is preferably a cured resin layer-forming composition. In addition, the cured resin layer can be composed of multiple layers, but from the viewpoint of productivity, it is preferably less than 2 layers, more preferably a single layer. In addition, from the aspect of not affecting the optical properties of the multiple layers, it is preferred that the cured resin layer is optically isotropic.

[0172] In this disclosure, the resin contained in the cured resin layer is sometimes referred to based on the functional group with the largest number among the functional groups contained. For example, when the number of acryloxy groups among the functional groups contained in the resin is the largest, the resin is referred to as an acrylic resin, and when the number of epoxy groups among the functional groups contained in the resin is the largest, the resin is referred to as an epoxy resin, etc.

[0173] The cured resin layer preferably includes at least one selected from the group consisting of acrylic resin, epoxy resin, oxetane resin, polyurethane resin and melamine resin. By including at least one resin as described above, the curability is high and the reliability when combined with the horizontally aligned liquid crystal cured film is easily improved.

[0174] The composition for forming a curable resin layer constituting the curable resin layer is a composition containing a curable polymerizable monomer such as a free radical polymerizable monomer, a cationic polymerizable monomer, a thermally polymerizable monomer as a curable material. From the perspective of high reaction speed and improved productivity, and easy improvement in reliability when combined with a horizontally oriented liquid crystal curing film, it is more preferable to contain a free radical polymerizable monomer or a cationic polymerizable monomer.

[0175] The cured resin layer preferably contains at least one selected from the group consisting of acrylic resin, epoxy resin, oxetane resin, polyurethane resin and melamine resin. By making the cured resin layer contain such a resin, the curability is high and the reliability when combined with the horizontal alignment liquid crystal cured film is easily improved.

[0176] The composition for forming the cured resin layer contains a curable polymerizable monomer as a curable material. As the polymerizable monomer, for example, free radical polymerizable monomers, cationic polymerizable monomers and thermal polymerizable monomers can be cited. From the aspects of high reaction speed and improved productivity, and the aspect of easy improvement of reliability when combined with a horizontally aligned liquid crystal cured film, the polymerizable monomer is preferably a free radical polymerizable monomer and a cationic polymerizable monomer.

[0177] As such radical polymerizable monomers, for example, (meth)acrylate compounds such as multifunctional (meth)acrylate compounds; urethane (meth)acrylate compounds such as multifunctional urethane (meth)acrylate compounds; epoxy (meth)acrylate compounds such as multifunctional epoxy (meth)acrylate compounds; carboxyl-modified epoxy (meth)acrylate compounds, polyester (meth)acrylate compounds, etc. These may be used alone or in combination of two or more.

[0178] From the viewpoint of improving reliability when combined with a horizontally aligned liquid crystal cured film, improving adhesion with adjacent layers, and improving productivity, the polymerizable monomer is preferably a polymerizable monomer having a (meth)acryloyloxy group, more preferably a multifunctional (meth)acrylate compound, and even more preferably a multifunctional acrylate compound.

[0179] Examples of the polyfunctional acrylate compound include a bifunctional (meth)acrylate monomer having two (meth)acryloyloxy groups in the molecule and a trifunctional or higher-functional (meth)acrylate monomer having three or more (meth)acryloyloxy groups in the molecule.

[0180] In the present specification, "(meth)acrylate" means "acrylate" or "methacrylate", "(meth)acryloyl" means "acryloyl" or "methacryloyl", and "polyfunctional (meth)acrylate compound" means a compound having two or more (meth)acryloyloxy groups in the molecule.

[0181] The multifunctional (meth)acrylate compound may be used alone or in combination of two or more. When two or more multifunctional (meth)acrylate compounds are used, the number of (meth)acryloyloxy groups contained in each multifunctional (meth)acrylate compound may be the same or different.

[0182] Examples of the monomer having two (meth)acryloyloxy groups in the molecule include alkylene glycol di(meth)acrylates such as ethylene glycol di(meth)acrylate, 1,3-butanediol di(meth)acrylate, 1,4-butanediol di(meth)acrylate, 1,6-hexanediol di(meth)acrylate, 1,9-nonanediol di(meth)acrylate, and neopentyl glycol di(meth)acrylate; and diethylene glycol di(meth)acrylate, triethylene glycol di(meth)acrylate, dipropylene glycol di(meth)acrylate, and tripropylene glycol di(meth)acrylate. esters, polyethylene glycol di(meth)acrylate, polypropylene glycol di(meth)acrylate, polybutylene glycol di(meth)acrylate and other polyoxyalkylene glycol di(meth)acrylates; di(meth)acrylates of halogen-substituted alkylene glycols such as tetrafluoroethylene glycol di(meth)acrylate; di(meth)acrylates of aliphatic polyols such as trimethylolpropane di(meth)acrylate, ditrimethylolpropane di(meth)acrylate, pentaerythritol di(meth)acrylate; hydrogenated dicyclopentadienyl di(meth)acrylate, tricyclodecane dimethanol di(meth)acrylate, etc. Di(meth)acrylate of hydrogenated dicyclopentadiene or tricyclodecanediol; di(meth)acrylate of dioxanediol or dioxanediol such as 1,3-dioxane-2,5-diyl di(meth)acrylate [alias: dioxanediol di(meth)acrylate]; di(meth)acrylate of bisphenol A or bisphenol F ethylene oxide adduct such as bisphenol A ethylene oxide adduct diacrylate and bisphenol F ethylene oxide adduct diacrylate; acrylic acid adduct of bisphenol A diglycidyl ether and acrylic acid adduct of bisphenol F diglycidyl ether Epoxy di(meth)acrylates of bisphenol A or bisphenol F; polysiloxane di(meth)acrylate; di(meth)acrylate of hydroxypivalic acid neopentyl glycol ester; 2,2-bis[4-(meth)acryloyloxyethoxyethoxyphenyl]propane; 2,2-bis[4-(meth)acryloyloxyethoxyethoxycyclohexyl]propane; di(meth)acrylate of 2-(2-hydroxy-1,1-dimethylethyl)-5-ethyl-5-hydroxymethyl-1,3-dioxane]; tris(hydroxyethyl)isocyanurate di(meth)acrylate, etc.

[0183] Examples of the monomer having three (meth)acryloyloxy groups in the molecule include glycerol tri(meth)acrylate, trimethylolpropane tri(meth)acrylate, ditrimethylolpropane tri(meth)acrylate, pentaerythritol tri(meth)acrylate, a reaction product of pentaerythritol tri(meth)acrylate and an acid anhydride, caprolactone-modified trimethylolpropane tri(meth)acrylate, caprolactone-modified pentaerythritol tri(meth)acrylate, ethylene oxide-modified trimethylolpropane tri(meth)acrylate, and the like. The invention also includes the following: polyol (meth)acrylate, ethylene oxide modified pentaerythritol tri (meth) acrylate, propylene oxide modified trimethylolpropane tri (meth) acrylate, propylene oxide modified pentaerythritol tri (meth) acrylate, isocyanurate tri (meth) acrylate, a reaction product of caprolactone modified pentaerythritol tri (meth) acrylate and an acid anhydride, a reaction product of ethylene oxide modified pentaerythritol tri (meth) acrylate and an acid anhydride, a reaction product of propylene oxide modified pentaerythritol tri (meth) acrylate and an acid anhydride, and the like.

[0184] Examples of the monomer having four (meth)acryloyloxy groups in the molecule include ditrimethylolpropane tetra(meth)acrylate, pentaerythritol tetra(meth)acrylate, dipentaerythritol tetra(meth)acrylate, tripentaerythritol tetra(meth)acrylate, caprolactone-modified pentaerythritol tetra(meth)acrylate, caprolactone-modified tripentaerythritol tetra(meth)acrylate, ethylene oxide-modified pentaerythritol tetra(meth)acrylate, ethylene oxide-modified tripentaerythritol tetra(meth)acrylate, propylene oxide-modified pentaerythritol tetra(meth)acrylate, and propylene oxide-modified tripentaerythritol tetra(meth)acrylate.

[0185] Examples of the monomer having five (meth)acryloyloxy groups in the molecule include dipentaerythritol penta(meth)acrylate, tripentaerythritol penta(meth)acrylate, a reaction product of dipentaerythritol penta(meth)acrylate and an acid anhydride, caprolactone-modified dipentaerythritol penta(meth)acrylate, caprolactone-modified tripentaerythritol penta(meth)acrylate, ethylene oxide-modified dipentaerythritol penta(meth)acrylate, ethylene oxide-modified tripentaerythritol penta(meth)acrylate, propylene oxide-modified dipentaerythritol penta(meth)acrylate, propylene oxide-modified tripentaerythritol penta(meth)acrylate, a reaction product of caprolactone-modified dipentaerythritol penta(meth)acrylate and an acid anhydride, a reaction product of ethylene oxide-modified dipentaerythritol penta(meth)acrylate and an acid anhydride, and a reaction product of propylene oxide-modified dipentaerythritol penta(meth)acrylate and an acid anhydride.

[0186] Examples of the monomer having six (meth)acryloyloxy groups in the molecule include dipentaerythritol hexa(meth)acrylate, tripentaerythritol hexa(meth)acrylate, caprolactone-modified dipentaerythritol hexa(meth)acrylate, caprolactone-modified tripentaerythritol hexa(meth)acrylate, ethylene oxide-modified dipentaerythritol hexa(meth)acrylate, ethylene oxide-modified tripentaerythritol hexa(meth)acrylate, propylene oxide-modified dipentaerythritol hexa(meth)acrylate, and propylene oxide-modified tripentaerythritol hexa(meth)acrylate.

[0187] Examples of the monomer having 7 (meth)acryloyloxy groups in the molecule include tripentaerythritol hepta(meth)acrylate, a reaction product of tripentaerythritol hepta(meth)acrylate and acid anhydride, caprolactone-modified tripentaerythritol hepta(meth)acrylate, a reaction product of caprolactone-modified tripentaerythritol hepta(meth)acrylate and acid anhydride, ethylene oxide-modified tripentaerythritol hepta(meth)acrylate, a reaction product of ethylene oxide-modified tripentaerythritol hepta(meth)acrylate and acid anhydride, propylene oxide-modified tripentaerythritol hepta(meth)acrylate, a reaction product of propylene oxide-modified tripentaerythritol hepta(meth)acrylate and acid anhydride, and the like.

[0188] Examples of the monomer having eight (meth)acryloyloxy groups in the molecule include tripentaerythritol octa(meth)acrylate, caprolactone-modified tripentaerythritol octa(meth)acrylate, ethylene oxide-modified tripentaerythritol octa(meth)acrylate, and propylene oxide-modified tripentaerythritol octa(meth)acrylate.

[0189] Examples of the cationically polymerizable monomer include epoxy compounds having an epoxy group and oxetane compounds having an oxetane group.

[0190] The epoxy compound is a polymerizable monomer having at least one epoxy group in the molecule. Examples of the epoxy compound include alicyclic epoxy compounds, aromatic epoxy compounds, and aliphatic epoxy compounds.

[0191] The alicyclic epoxy compound is a compound having at least one epoxy group directly bonded to an alicyclic ring in the molecule. Examples of the alicyclic epoxy compound include 3,4-epoxycyclohexanecarboxylic acid 3,4-epoxycyclohexylmethyl ester, 3,4-epoxy-6-methylcyclohexanecarboxylic acid 3,4-epoxy-6-methylcyclohexanecarboxylic acid 3,4-epoxy-6-methylcyclohexanemethyl ester, ethylene bis(3,4-epoxycyclohexanecarboxylate), adipate bis(3,4-epoxycyclohexylmethyl) ester, adipate bis(3,4-epoxy-6-methylcyclohexylmethyl) ester, diethylene glycol bis(3,4-epoxycyclohexylmethyl ether), and ethylene glycol bis(3,4-epoxycyclohexylmethyl) ether. These alicyclic epoxy compounds may be used alone or in combination of two or more.

[0192] Aromatic epoxy compounds are compounds having an aromatic ring and an epoxy group in the molecule. Specific examples thereof include bisphenol-type epoxy compounds or oligomers thereof such as diglycidyl ether of bisphenol A, diglycidyl ether of bisphenol F, and diglycidyl ether of bisphenol S; Novolac-type epoxy resins such as phenol Novolac epoxy resin, cresol Novolac epoxy resin, and hydroxybenzaldehyde phenol Novolac epoxy resin; polyfunctional epoxy compounds such as glycidyl ether of 2,2',4,4'-tetrahydroxydiphenylmethane and glycidyl ether of 2,2',4,4'-tetrahydroxybenzophenone; and polyfunctional epoxy resins such as epoxidized polyvinylphenol. These aromatic epoxy compounds may be used alone or in combination of two or more.

[0193] As for the hydrogenated epoxy compounds, the nuclear hydrogenated products of the above aromatic epoxy compounds become hydrogenated epoxy compounds. They can be produced by the following method: for the aromatic polyhydroxy compounds, typically bisphenols, which are the raw materials of the corresponding aromatic epoxy compounds, a hydrogenation reaction is selectively carried out in the presence of a catalyst and under pressure, and the polyols, typically hydrogenated bisphenols, obtained are used as raw materials, and are reacted with epichlorohydrin to form chlorohydrin ethers, and further intramolecular ring closure is carried out using a base. These hydrogenated epoxy compounds can be used alone or in combination of two or more.

[0194] Aliphatic epoxy compounds include polyglycidyl ethers of aliphatic polyols or alkylene oxide adducts thereof. Specific examples thereof include diglycidyl ether of neopentyl glycol, diglycidyl ether of 1,4-butanediol, diglycidyl ether of 1,6-hexanediol, triglycidyl ether of glycerol, triglycidyl ether of trimethylolpropane, diglycidyl ether of polyethylene glycol, diglycidyl ether of propylene glycol, polyglycidyl ether of polyether polyols obtained by adding one or more alkylene oxides (ethylene oxide, propylene oxide) to aliphatic polyols such as ethylene glycol, propylene glycol, and glycerol. These aliphatic epoxy compounds can be used alone or in combination of two or more.

[0195] The oxetane compound is a compound containing at least one oxetane group in the molecule, and specific examples thereof include 3-ethyl-3-hydroxymethyloxetane (also referred to as oxetanol), 2-ethylhexyloxetane, 1,4-bis[{(3-ethyloxetane-3-yl)methoxy}methyl]benzene (also referred to as xylylenebisoxetane), 3-ethyl-3[{(3-ethyloxetane-3-yl)methoxy}methyl]oxetane, 3-ethyl-3-(phenoxymethyl)oxetane, and 3-(cyclohexyloxy)methyl-3-ethyloxetane.

[0196] Examples of the thermally polymerizable monomers include melamine compounds, such as hexamethoxymethylmelamine, hexaethoxymethylmelamine, hexapropoxymethylmelamine, and hexabutoxymethylmelamine. The melamine compounds may be used alone or in combination of two or more.

[0197] In addition, as other polymerizable monomers, a combination of an isocyanate compound and an alcohol compound having a hydroxyl group in the molecule can be cited, and polyurethane resin can be manufactured. The isocyanate compound used to manufacture polyurethane resin and urea resin usually has more than 2 isocyanate groups (-NCO) in the molecule, and various diisocyanates of aromatic, aliphatic or alicyclic can be used. As a specific example, tetramethylene diisocyanate, hexamethylene diisocyanate, isophorone diisocyanate, 2,4-toluene diisocyanate, 4,4'-diphenyl diisocyanate, 1,5-naphthalene diisocyanate, 3,3'-dimethyl-4,4'-diphenyl diisocyanate, xylene diisocyanate, trimethyl hexamethylene diisocyanate, 4,4'-diphenylmethane diisocyanate, and the nuclear hydrogenation of diisocyanates with aromatic rings therein can be cited. In addition, the alcohol compound used for the polyurethane resin generally has two or more hydroxyl groups in the molecule, and examples thereof include ethylene glycol, 1,2-propylene glycol, 1,3-propylene glycol, diethylene glycol, dipropylene glycol, neopentyl glycol, 1,3-butylene glycol, 1,4-butylene glycol, 1,6-hexanediol, 1,9-nonanediol, 1,10-decanediol, 2,2,4-trimethyl-1,3-pentanediol, 3-methyl-1,5-pentanediol, neopentyl glycol ester of hydroxypivalic acid, 1,4-cyclohexanediol, spirodiol, tricyclodecane dimethanol, bisphenol A, hydrogenated bisphenol A, trimethylolethane, trimethylolpropane, glycerol, 3-methylpentane-1,3,5-triol, pentaerythritol, dipentaerythritol, tripentaerythritol, glucose, and the like.

[0198] The above-mentioned polymerizable monomer can be appropriately selected from the viewpoints of suppressing the warping caused by heating during and after curing, improving processing characteristics, adjusting the adhesion with the substrate and the liquid crystal curing film, improving productivity, improving solvent resistance, and improving reliability when combined with a horizontally oriented liquid crystal curing film. In the present disclosure, the cured resin layer preferably includes at least one selected from the group consisting of acrylic resin, epoxy resin, oxetane resin, polyurethane resin and melamine resin. In addition, for example, two or more free radical polymerizable monomers can be used, and free radical polymerizable monomers can also be combined with cationic polymerizable monomers. In particular, from the viewpoint of improving productivity, it is preferred to contain free radical polymerizable monomers.

[0199] In the composition for forming a cured resin layer, in addition to the polymerizable monomer, additives such as a photopolymerization initiator, a thermal polymerization initiator, a solvent, an antioxidant, a photosensitizer, a leveling agent, an antioxidant, a chain transfer agent, a light stabilizer, a tackifier, a filler, a flow regulator, a plasticizer, a defoamer, a pigment, an antistatic agent, and a UV absorber may be further included. These additives are generally 0.1 to 15% by mass relative to the mass of the solid content of the composition for forming a cured resin layer. The so-called solid content of the composition for forming a cured resin layer, when the composition for forming a cured resin layer contains a solvent, refers to the total amount of the components after removing the solvent from the composition.

[0200] In the composition for forming a cured resin layer, the content of the polymerizable monomer is preferably 50 parts by mass or more, more preferably 60 parts by mass or more, relative to 100 parts by mass of the solid content of the composition. If it is within the above range, it is easy to improve the reliability when combined with a horizontally aligned liquid crystal cured film.

[0201] The composition for forming the cured resin layer preferably includes a polymerization initiator. As the polymerization initiator, photopolymerization initiators, thermal polymerization initiators, etc. can be cited, but from the viewpoint of improving productivity, photopolymerization initiators are preferably used. Photopolymerization initiators are not particularly limited as long as they are substances that can initiate the curing of polymerizable monomers by irradiation with active energy rays such as visible light, ultraviolet rays, X-rays, and electron beams. Photoradical polymerization initiators and photocationic polymerization initiators can be appropriately used according to the type of polymerizable monomer. As photoradical polymerization initiators and photocationic polymerization initiators, specifically, polymerization initiators similar to the polymerization initiators exemplified in the above text as polymerization initiators that can be combined with the polymerizable liquid crystal composition that forms a horizontally oriented liquid crystal cured film can be cited.

[0202] When the composition for forming a cured resin layer contains a polymerization initiator, the content of the polymerization initiator is preferably 0.1 to 10 parts by mass, more preferably 0.5 to 7 parts by mass, relative to 100 parts by mass of the total amount of the curable compound. If the content of the polymerization initiator is above the lower limit, the polymerization initiation ability can be fully exhibited, and if the content of the polymerization initiator is below the upper limit, the polymerization initiator is not likely to remain.

[0203] When the composition for forming a cured resin layer contains a solvent, it can be appropriately selected based on the viewpoint of fully dissolving the polymerizable monomer, polymerization initiator, etc. added to the composition for forming a cured resin layer and not dissolving the substrate. For example, a solvent that can be used in a polymerizable liquid crystal composition for forming a horizontally aligned liquid crystal cured film can be used. The content of the solvent can be 1 to 10,000 parts by mass, preferably 10 to 1,000 parts by mass, and more preferably 20 to 500 parts by mass, relative to 100 parts by mass of the total amount of the components contained in the composition for forming a cured resin layer.

[0204] In the laminate of the present disclosure, the cured resin layer is preferably optically isotropic. If the cured resin layer is optically isotropic, when combined with a horizontally aligned liquid crystal cured film, the optical properties of the horizontally aligned liquid crystal cured film will not be affected, and a laminate with high optical properties can be obtained.

[0205] When the laminate includes a cured resin layer, the lamination order of the layers of the laminate can be appropriately selected, but the laminate preferably has a laminate structure including a horizontally aligned liquid crystal cured film, a horizontally aligned film, and a cured resin layer in this order. The laminate may further include a tackiness adhesive layer.

[0206] The laminate can be produced, for example, by a method including the following steps.

[0207] Cured resin layer forming step: a step of forming a cured resin layer

[0208] Horizontal alignment film forming process: Process of forming a horizontal alignment film

[0209] Horizontally aligned liquid crystal cured film forming step: a step of forming a horizontally aligned liquid crystal cured film (optical film) on a horizontally aligned film

[0210] (Cured Resin Layer Formation Step)

[0211] The cured resin layer can be obtained, for example, by applying the composition for forming a cured resin layer onto a substrate and, if a solvent is contained, drying and removing the solvent to cure the polymerizable monomer.

[0212] As a substrate, for example, a glass substrate, a film substrate, etc. can be cited, but from the viewpoint of processability, a resin film substrate is preferably used. As a resin constituting a film substrate, for example, polyolefins such as polyethylene, polypropylene, and norbornene polymers can be cited; cyclic olefin resins; polyvinyl alcohol; polyethylene terephthalate; polymethacrylate; polyacrylate; cellulose esters such as cellulose triacetate, cellulose diacetate, and cellulose acetate propionate; polyethylene naphthalate; polycarbonate; polysulfone; polyethersulfone; polyetherketone; plastics such as polyphenylene sulfide and polyphenylene ether. Such resins can be made into films by known means such as solvent casting and melt extrusion to form substrates. For the surface of the substrate (for example, the surface to be bonded to the adhesive layer), surface treatments such as mold release treatment, corona treatment, and plasma treatment such as silicone treatment can be implemented.

[0213] As the substrate, commercially available products can be used. Examples of commercially available cellulose ester substrates include cellulose ester substrates manufactured by Fuji Photo Film Co., Ltd., such as Fujitac Film; cellulose ester substrates manufactured by Konica Minolta Opto Co., Ltd., such as "KC8UX2M", "KC8UY", and "KC4UY", etc. Examples of commercially available cyclic olefin resins include cyclic olefin resins manufactured by Ticona (Germany), such as "Topas (registered trademark)"; cyclic olefin resins manufactured by JSR Corporation, such as "Arton (registered trademark)"; cyclic olefin resins manufactured by Zeon Co., Ltd., such as "ZEONOR (Registered Trademark)" and "ZEONEX (Registered Trademark)"; and cyclic olefin resins manufactured by Mitsui Chemicals, Inc., such as "Apel (Registered Trademark). Commercially available cyclic olefin resin substrates may also be used. Examples of commercially available cyclic olefin resin substrates include cyclic olefin resin substrates such as "Esushina (registered trademark)" and "SCA40 (registered trademark)" manufactured by Sekisui Chemical Co., Ltd.; cyclic olefin resin substrates such as "Zeonor Film (registered trademark)" manufactured by OPTES Co., Ltd.; and cyclic olefin resin substrates such as "Arton Film (registered trademark)" manufactured by JSR Co., Ltd.

[0214] The thickness of the substrate is usually 5 to 300 μm, preferably 10 to 150 μm, from the viewpoint of thinning and easy peeling of the substrate.

[0215] Examples of a method for applying the composition for forming a cured resin layer to a substrate include known methods such as spin coating, extrusion, gravure coating, die coating, bar coating, and applicator coating, and printing methods such as flexographic printing.

[0216] When the composition for forming a cured resin layer contains a solvent, examples of a method for removing the solvent by drying include natural drying, ventilation drying, heating drying, and reduced pressure drying.

[0217] (Horizontal Alignment Film Formation Step)

[0218] When the horizontal alignment film included in the laminate is a rubbed alignment film, an alignment polymer composition is applied on the cured resin layer, and the solvent is removed to form a coating film. Then, the coating film is rubbed to obtain a horizontal alignment film.

[0219] Examples of a method for coating the oriented polymer composition on the cured resin layer include known methods such as spin coating, extrusion, gravure coating, die coating, bar coating, and applicator coating, and printing methods such as flexographic printing.

[0220] Examples of a method for removing the solvent from the oriented polymer composition by drying include natural drying, ventilation drying, heating drying, and reduced-pressure drying.

[0221] As a rubbing treatment method, for example, there can be mentioned a method of bringing the coating film into contact with a rubbing roller wound with a rubbing cloth and rotating. During the rubbing treatment, if masking is performed, a plurality of regions (patterns) with different orientation directions can be formed on the orientation film.

[0222] When the horizontal alignment film is a photo alignment film, the photo alignment film-forming composition is applied on the cured resin layer, the solvent is removed, and then polarized light is irradiated to obtain the photo horizontal alignment film. The polarized light irradiated is preferably polarized UV light.

[0223] Examples of a method for coating the photo-alignment film-forming composition on the cured resin layer and a method for removing the solvent from the coated photo-alignment film-forming composition include the same methods as those exemplified for the aligning polymer composition.

[0224] When irradiating polarized light, it can be a method of directly irradiating polarized UV light to the product obtained by removing the solvent from the composition for forming a light alignment film applied on the surface of the horizontal alignment film to be formed. In addition, it is particularly preferred that the polarized light is substantially parallel light. The wavelength of the irradiated polarized light is preferably a wavelength in the wavelength region where the photoreactive group of the polymer or monomer having a photoreactive group can absorb light energy. Specifically, it is preferably UV (ultraviolet light) in the range of 250 to 400nm in wavelength. As the light source used in the polarized light irradiation, xenon lamps, high-pressure mercury lamps, ultra-high-pressure mercury lamps, metal halide lamps, ultraviolet lasers such as KrF and ArF can be cited, and high-pressure mercury lamps, ultra-high-pressure mercury lamps and metal halide lamps are more preferred. Among them, high-pressure mercury lamps, ultra-high-pressure mercury lamps and metal halide lamps are preferred because of the large luminous intensity of ultraviolet rays with a wavelength of 313nm. Polarized UV light can be irradiated by passing light from a light source through an appropriate polarizer. As the polarizer, a polarizing filter, a polarizing prism such as Glan-Thompson or Glan-Taylor, or a wire grid type polarizer can be used.

[0225] It should be noted that, if masking is performed during rubbing or polarized light irradiation, a plurality of regions (patterns) in which the directions of liquid crystal alignment are different can be formed.

[0226] As methods for obtaining a grooved oriented film, there are: a method of exposing the surface of a photosensitive polyimide film through an exposure mask having a slit in a pattern shape, and then developing and rinsing to form a concave-convex pattern; a method of forming a layer of a pre-cured UV-curable resin on a plate-like original plate having grooves on its surface, transferring the formed resin layer to a cured resin layer, and then curing the layer; and a method of pressing a roll-like original plate having a plurality of grooves onto a film of a pre-cured UV-curable resin formed on a cured resin layer to form concave-convex patterns, and then curing the layer.

[0227] When the laminate does not include a cured resin layer, a horizontal alignment film may be formed on the substrate.

[0228] (Horizontally-aligned liquid crystal cured film formation step)

[0229] In this process, a polymerizable liquid crystal composition is applied to the horizontal alignment film to obtain a coating film. The obtained coating film is heated to a temperature above the liquid crystal phase transition temperature of the polymerizable liquid crystal compound contained in the polymerizable liquid crystal composition. Thus, while the solvent is dried and removed from the coating film, the polymerizable liquid crystal compound is oriented in the horizontal direction.

[0230] The heating temperature of the coating film can be appropriately determined by considering the materials of the polymerizable liquid crystal compound used and the substrate forming the coating film. In order to remove the solvent contained in the polymerizable liquid crystal composition while making the polymerizable liquid crystal compound in a horizontal orientation state, the heating temperature is preferably 3°C or more, more preferably 5°C or more, higher than the liquid crystal phase (nematic phase) transition temperature of the polymerizable liquid crystal compound. The upper limit of the heating temperature is not particularly limited, but in order to avoid damage to the coating film, substrate, etc. caused by heating, it is preferably 180°C or less, more preferably 150°C or less. The nematic transition temperature can be measured using, for example, a polarizing microscope with a temperature adjustment table, a differential scanning calorimeter (DSC), a thermogravimetric differential thermal analyzer (TG-DTA), etc.

[0231] The heating time can be appropriately determined according to the heating temperature, the type of polymerizable liquid crystal compound used, the type of solvent, its boiling point and its amount, etc. The heating time is, for example, 0.5 to 10 minutes, preferably 0.5 to 5 minutes.

[0232] The removal of solvent from the coating film can be carried out simultaneously with the heating of the polymerizable liquid crystal compound to the nematic phase transition temperature or above, or it can be carried out independently, but from the viewpoint of improving productivity, it is preferably carried out simultaneously. The removal of solvent from the coating film is usually carried out simultaneously with the heating of the polymerizable liquid crystal compound to the nematic phase transition temperature or above, and it is also possible to provide a pre-drying process for removing the solvent in the coating film appropriately under the condition that the polymerizable liquid crystal compound contained in the coating film obtained by the polymerizable liquid crystal composition is not polymerized before the heating of the polymerizable liquid crystal compound to the liquid crystal phase transition temperature or above. As the drying method in the pre-drying process, natural drying method, ventilation drying method, heating drying and reduced pressure drying method, etc. can be cited, and the drying temperature (heating temperature) in the drying process can be appropriately determined according to the type of polymerizable liquid crystal compound used, the type of solvent, its boiling point and its amount, etc.

[0233] Then, in the obtained dry coating, while maintaining the horizontal orientation state of the polymerizable liquid crystal compound, the polymerizable liquid crystal compound is polymerized to form a horizontally oriented liquid crystal cured film. As a polymerization method, it is preferably a photopolymerization method, and a horizontally oriented liquid crystal cured film can be formed by irradiating light from the coating surface side of the polymerizable liquid crystal composition. In photopolymerization, as the light irradiated to the dry coating, it can be appropriately selected according to the type of photopolymerization initiator contained in the dry coating, the type of polymerizable liquid crystal compound (especially the type of polymerizable group possessed by the polymerizable liquid crystal compound) and its amount. As a specific example, one or more light selected from the group consisting of visible light, ultraviolet light, infrared light, X-rays, α rays, β rays and γ rays, and active electron rays can be cited. Among them, from the aspect of easily controlling the progress of the polymerization reaction, it is preferably ultraviolet light that can be used as a photopolymerization device and a device widely used in the art. It is preferred that the type of polymerizable liquid crystal compound and the photopolymerization initiator contained in the polymerizable liquid crystal composition be pre-selected in a manner that can be photopolymerized using ultraviolet light. In addition, during polymerization, the polymerization temperature can be controlled by irradiating the dried coating with light while cooling it with an appropriate cooling means. If the polymerization of the polymerizable liquid crystal compound is carried out at a lower temperature by adopting such a cooling means, a horizontally aligned liquid crystal cured film can be properly formed even if a substrate with low heat resistance is used as the substrate.

[0234] As the light source of active energy rays, for example, there can be mentioned a low-pressure mercury lamp, a medium-pressure mercury lamp, a high-pressure mercury lamp, an ultra-high-pressure mercury lamp, a xenon lamp, a halogen lamp, a carbon arc lamp, a tungsten lamp, a gallium lamp, an excimer laser, an LED light source emitting light in a wavelength range of 380 to 440 nm, a chemical lamp, a black light lamp, a microwave-excited mercury lamp, and a metal halide lamp.

[0235] The ultraviolet irradiation intensity is, for example, 10 to 3,000 mW / cm 2 The irradiation time is, for example, 0.1 second to 10 minutes, preferably 0.1 second to 5 minutes, more preferably 0.1 second to 3 minutes, and even more preferably 0.1 second to 1 minute. When irradiation is performed once or more times with such an ultraviolet irradiation intensity, the cumulative light amount is, for example, 10 to 3,000 mJ / cm 2 , preferably 50 to 2,000 mJ / cm 2 , more preferably 100 to 1,000 mJ / cm 2 .

[0236] When the laminate further includes a tackiness adhesive layer, examples of the tackiness adhesive constituting the tackiness adhesive include pressure-sensitive adhesives, dry curing adhesives, and chemical reaction adhesives. Examples of the chemical reaction adhesive include active energy ray curing adhesives.

[0237] Pressure-sensitive adhesives usually contain polymers and may contain solvents. Examples of polymers include acrylic polymers, silicone polymers, polyesters, polyurethanes, and polyethers. Among them, acrylic adhesives containing acrylic polymers have excellent optical transparency, appropriate wettability, cohesive force, and excellent adhesion. In addition, they have high weather resistance and heat resistance, and are not prone to floating or peeling under heating or humidification conditions, so they are preferred.

[0238] The acrylic polymer is preferably a copolymer of a (meth)acrylate in which the alkyl group of the ester portion is an alkyl group having 1 to 20 carbon atoms such as methyl, ethyl or butyl, and a (meth)acrylic monomer having a functional group such as (meth)acrylic acid or hydroxyethyl (meth)acrylate.

[0239] The pressure-sensitive adhesive containing such a copolymer has excellent adhesiveness, and even when it is removed after being attached to the transfer body, no adhesive residue is left on the transfer body, and it can be removed relatively easily, so it is preferred. The glass transition temperature of the acrylic polymer is preferably 25°C or less, more preferably 0°C or less. The mass average molecular weight of such an acrylic polymer is preferably 100,000 or more.

[0240] As the solvent, the same solvent as that which can be used in the polymerizable liquid crystal composition and the like can be cited. The pressure-sensitive adhesive may contain a light diffuser. The light diffuser is an additive that imparts light diffusivity to the adhesive, and it is sufficient that it is microparticles having a refractive index different from that of the polymer contained in the adhesive. As the light diffuser, microparticles formed of inorganic compounds and microparticles formed of organic compounds (polymers) can be cited. Most polymers contained in the adhesive as an effective ingredient, including acrylic polymers, have a refractive index of 1.4 to 1.6, and therefore, it is preferably selected appropriately from light diffusers having a refractive index of 1.2 to 1.8. The refractive index difference between the polymer contained in the adhesive as an effective ingredient and the light diffuser is usually 0.01 or more, and is preferably 0.01 to 0.2 from the viewpoint of the brightness and display properties of the display device. The microparticles used as the light diffuser are preferably spherical microparticles and microparticles close to monodisperse, and microparticles having an average particle size of 2 to 6 μm are more preferred. The refractive index can be measured using a conventional minimum deflection angle method or an Abbe refractometer.

[0241] As microparticles formed of inorganic compounds, aluminum oxide (refractive index 1.76) and silicon oxide (refractive index 1.45) can be cited. As microparticles formed of organic compounds (polymers), melamine beads (refractive index 1.57), polymethyl methacrylate beads (refractive index 1.49), methyl methacrylate / styrene copolymer resin beads (refractive index 1.50-1.59), polycarbonate beads (refractive index 1.55), polyethylene beads (refractive index 1.53), polystyrene beads (refractive index 1.6), polyvinyl chloride beads (refractive index 1.46), and silicone resin beads (refractive index 1.46) can be cited. The content of the light diffusing agent is, for example, 3 to 30 parts by mass relative to 100 parts by mass of the polymer.

[0242] The thickness of the pressure-sensitive adhesive can be determined according to its adhesion, etc., and therefore is not particularly limited, and is, for example, 1 μm to 40 μm. In view of processability, durability, etc., the thickness is preferably 3 μm to 25 μm, and more preferably 5 μm to 20 μm. By making the thickness of the adhesive layer formed by the adhesive 5 μm to 20 μm, the brightness when the display device is viewed from the front and the brightness when the display device is viewed from an oblique direction can be maintained, and it is not easy to produce stains and blurs on the displayed image.

[0243] The dry curing adhesive may contain a solvent. As the dry curing adhesive, there can be mentioned a polymer or polyurethane resin containing a monomer having a protic functional group such as a hydroxyl group, a carboxyl group or an amino group and an ethylenically unsaturated group as a main component, and further containing a composition of a crosslinking agent or a curing compound such as a polyaldehyde, an epoxy compound, an epoxy resin, a melamine compound, a zirconium oxide compound, and a zinc compound. As the polymer of a monomer having a protic functional group such as a hydroxyl group, a carboxyl group or an amino group and an ethylenically unsaturated group, there can be mentioned ethylene-maleic acid copolymers, itaconic acid copolymers, acrylic acid copolymers, acrylamide copolymers, saponified products of polyvinyl acetate, and polyvinyl alcohol resins.

[0244] Examples of the polyvinyl alcohol-based resin include polyvinyl alcohol, partially saponified polyvinyl alcohol, completely saponified polyvinyl alcohol, carboxyl-modified polyvinyl alcohol, acetoacetyl-modified polyvinyl alcohol, hydroxymethyl-modified polyvinyl alcohol, and amino-modified polyvinyl alcohol. The content of the polyvinyl alcohol-based resin in the aqueous adhesive is, for example, 1 to 10 parts by mass, preferably 1 to 5 parts by mass, relative to 100 parts by mass of water.

[0245] As polyurethane resins, polyester ionomer polyurethane resins and the like can be cited. The polyester ionomer polyurethane resins referred to herein are polyurethane resins having a polyester skeleton and into which a small amount of ionic components (hydrophilic components) are introduced. The ionomer polyurethane resins are emulsified in water without using an emulsifier to form an emulsion, so that they can be made into water-based adhesives. When using polyester ionomer polyurethane resins, it is effective to use a water-soluble epoxy compound as a crosslinking agent.

[0246] As epoxy resin, polyamide epoxy resin etc. obtained by reacting epichlorohydrin with polyamide polyamine obtained by reaction of polyalkylene polyamine such as diethylenetriamine or triethylenetetramine with dicarboxylic acid such as adipic acid etc. can be cited. As commercially available products of the polyamide epoxy resin, Sumirez resin (registered trademark) 650 and Sumirez resin 675 (the above are made by Sumika Chemtex Co., Ltd.), WS-525 (made by Japan PMC Co., Ltd.) etc. can be cited. When epoxy resin is matched, its addition amount is, for example, 1 to 100 parts by mass, preferably 1 to 50 parts by mass, relative to 100 parts by mass of polyvinyl alcohol resin.

[0247] The thickness of the adhesive layer formed of the drying-curing adhesive is, for example, 0.001 to 5 μm, preferably 0.01 to 2 μm, and more preferably 0.01 to 0.5 μm. If the adhesive layer formed of the drying-curing adhesive is too thick, the appearance is likely to be poor.

[0248] The active energy ray-curable adhesive may contain a solvent. The so-called active energy ray-curable adhesive is an adhesive that is cured by irradiation with active energy rays. Examples of active energy ray-curable adhesives include cationic polymerizable adhesives containing epoxy compounds and cationic polymerization initiators, free radical polymerizable adhesives containing acrylic curing components and free radical polymerization initiators, adhesives containing both cationic polymerizable curing components such as epoxy compounds and free radical polymerizable curing components such as acrylic compounds and further containing cationic polymerization initiators and free radical polymerization initiators, and adhesives that do not contain these polymerization initiators and can be cured by irradiation with electron beams.

[0249] The active energy ray-curable adhesive is preferably a radically polymerizable active energy ray-curable adhesive containing an acrylic curing component and a photo-radical polymerization initiator, or a cationic polymerizable active energy ray-curable adhesive containing an epoxy compound and a photo-cationic polymerization initiator. As acrylic curing components, (meth)acrylates such as methyl (meth)acrylate and hydroxyethyl (meth)acrylate and (meth)acrylic acid can be cited. The active energy ray-curable adhesive containing an epoxy compound can also contain compounds other than the epoxy compound. As compounds other than the epoxy compound, oxetane compounds, acrylic compounds, etc. can be cited.

[0250] Examples of the photoradical polymerization initiator and the photocationic polymerization initiator include the above-mentioned photoradical polymerization initiators and the photocationic polymerization initiators. The content of the radical polymerization initiator and the cationic polymerization initiator is, for example, 0.5 to 20 parts by mass, preferably 1 to 15 parts by mass, relative to 100 parts by mass of the active energy ray-curable adhesive.

[0251] The active energy ray-curable adhesive may further contain an ion trapping agent, an antioxidant, a chain transfer agent, a tackifier, a thermoplastic resin, a filler, a flow regulator, a plasticizer, a defoaming agent, and the like.

[0252] In this specification, the so-called active energy ray is defined as an energy ray that can decompose a compound that can generate active species to generate active species. As such active energy rays, visible light, ultraviolet rays, infrared rays, X-rays, α rays, β rays, γ rays and electron rays can be cited, preferably ultraviolet rays and electron rays. The preferred ultraviolet irradiation conditions are the same as those for the polymerization of the aforementioned polymerizable liquid crystal compound.

[0253] The laminate may include other layers such as a vertically aligned liquid crystal cured film and other aligned liquid crystal cured films.

[0254] [Polarizing plate]

[0255] The polarizing plate according to the present embodiment includes a polarizing film and the optical film according to the above embodiment. The polarizing plate may include a polarizing film and the laminate according to the above embodiment.

[0256] (Polarizing film)

[0257] The polarizing film is a film having a polarizing function, and examples thereof include a stretched film adsorbed with a dye having absorption anisotropy, a film including a film coated with a dye having absorption anisotropy as a polarizer, etc. As a dye having absorption anisotropy, for example, a dichroic dye can be mentioned.

[0258] The polarizer can be produced, for example, through the following steps (1) to (4). In this way, a stretched film to which a dye having absorption anisotropy is adsorbed can be obtained as a polarizer.

[0259] Step (1): Step of uniaxially stretching a polyvinyl alcohol-based resin film

[0260] Step (2): a step of dyeing a polyvinyl alcohol-based resin film with a dichroic dye to adsorb the dichroic dye

[0261] Step (3): a step of treating the polyvinyl alcohol-based resin film having the dichroic dye adsorbed thereon with an aqueous boric acid solution

[0262] Step (4): a step of washing with water after treating with an aqueous boric acid solution

[0263] The polyvinyl alcohol resin can be obtained by saponifying a polyvinyl acetate resin. As the polyvinyl acetate resin, in addition to polyvinyl acetate which is a homopolymer of vinyl acetate, copolymers of vinyl acetate and other monomers copolymerizable therewith can be used. Examples of other monomers copolymerizable with vinyl acetate include unsaturated carboxylic acids, olefins, vinyl ethers, unsaturated sulfonic acids, and acrylamides having an ammonium group.

[0264] The saponification degree of the polyvinyl alcohol resin is, for example, 85 to 100 mol%, preferably 98 mol% or more. The polyvinyl alcohol resin may be modified, and for example, polyvinyl formal or polyvinyl acetal modified with aldehydes may be used. The polymerization degree of the polyvinyl alcohol resin is, for example, 1,000 to 10,000, preferably 1,500 to 5,000.

[0265] The film made of such a polyvinyl alcohol-based resin can be used as a raw film of a polarizing film. The method of forming the polyvinyl alcohol-based resin into a film is not particularly limited, and the film can be formed by a known method. The film thickness of the polyvinyl alcohol-based raw film can be, for example, 10 to 150 μm.

[0266] The uniaxial stretching of the polyvinyl alcohol resin film can be performed before, at the same time as, or after dyeing based on a dichroic pigment. In the case of uniaxial stretching after dyeing, the uniaxial stretching can be performed before or during the boric acid treatment. In addition, the uniaxial stretching can be performed in multiple stages thereof. When the uniaxial stretching is performed, the uniaxial stretching can be performed between rollers having different peripheral speeds, or the uniaxial stretching can be performed using a hot roller. In addition, the uniaxial stretching can be dry stretching performed in the atmosphere, or wet stretching performed in a state where the polyvinyl alcohol resin film is swollen with a solvent. The stretching ratio is, for example, 3 to 8 times.

[0267] The polyvinyl alcohol-based resin film can be dyed with a dichroic dye by, for example, a method of immersing the polyvinyl alcohol-based resin film in an aqueous solution containing a dichroic dye.

[0268] As the dichroic pigment, specifically, iodine and dichroic organic dyes can be used. As dichroic organic dyes, dichroic direct dyes formed by disazo compounds such as CI Direct Red (DIRECT RE D) 39, and dichroic direct dyes formed by compounds such as triazo and tetrakis azo can be cited. For the polyvinyl alcohol-based resin film, it is preferably immersed in water before dyeing.

[0269] When iodine is used as a dichroic pigment, a method of dyeing a polyvinyl alcohol-based resin film by immersing it in an aqueous solution containing iodine and potassium iodide can generally be adopted. The content of iodine in the aqueous solution is, for example, 0.01 to 1 part by mass relative to 100 parts by mass of water. In addition, the content of potassium iodide is, for example, 0.5 to 20 parts by mass relative to 100 parts by mass of water. The temperature of the aqueous solution used for dyeing is, for example, 20 to 40° C. In addition, the immersion time (dyeing time) in the aqueous solution is, for example, 20 to 1,800 seconds.

[0270] On the other hand, when a dichroic organic dye is used as the dichroic pigment, for example, a method of dyeing the polyvinyl alcohol-based resin film by immersing the film in an aqueous solution containing a water-soluble dichroic dye can be adopted. The content of the dichroic organic dye in the aqueous solution is, for example, 1×10 -4 ~10 parts by mass, preferably 1×10 -3 ~1 mass part, more preferably 1×10 -3 ~1×10 -2 The aqueous solution may contain an inorganic salt such as sodium sulfate as a dyeing auxiliary. The temperature of the dichroic dye aqueous solution used for dyeing is, for example, 20 to 80° C. In addition, the immersion time (dyeing time) in the aqueous solution is, for example, 10 to 1,800 seconds.

[0271] The boric acid treatment after dyeing with a dichroic pigment can be performed, for example, by immersing the dyed polyvinyl alcohol-based resin film in an aqueous boric acid solution. The content of boric acid in the aqueous boric acid solution is, for example, 2 to 15 parts by mass, preferably 5 to 12 parts by mass, relative to 100 parts by mass of water. When iodine is used as a dichroic pigment, the aqueous boric acid solution preferably contains potassium iodide, in which case the content of potassium iodide is, for example, 0.1 to 15 parts by mass, preferably 5 to 12 parts by mass, relative to 100 parts by mass of water. The immersion time in the aqueous boric acid solution is, for example, 60 to 1,200 seconds, preferably 150 to 600 seconds, and more preferably 200 to 400 seconds. The temperature of the boric acid treatment is, for example, above 50°C, preferably 50 to 85°C, and more preferably 60 to 80°C.

[0272] The polyvinyl alcohol-based resin film after the boric acid treatment may be subjected to a water washing treatment. The water washing treatment may be performed, for example, by immersing the polyvinyl alcohol-based resin film treated with boric acid in water. The temperature of the water in the water washing treatment is, for example, 5 to 40° C. The immersion time is, for example, 1 to 120 seconds.

[0273] A drying treatment can be performed after washing to obtain a polarizer. The drying treatment can be performed using, for example, a hot air dryer or a far-infrared heater. The temperature of the drying treatment is, for example, 30 to 100° C., preferably 50 to 80° C. The time of the drying treatment is, for example, 60 to 600 seconds, preferably 120 to 600 seconds. By drying, the moisture content of the polarizer can be reduced to a practical level. The moisture content is, for example, 5 to 20% by weight, preferably 8 to 15% by weight. If the moisture content is less than 5% by weight, the flexibility of the polarizer is impaired, and sometimes the polarizer is damaged or broken after it is dried. In addition, if the moisture content is higher than 20% by weight, there is a possibility that the thermal stability of the polarizer will deteriorate.

[0274] The thickness of the polarizer is preferably 5 to 40 μm.

[0275] As the film formed by coating with anisotropic pigment, coating comprising a composition having a dichroic pigment with liquid crystal or a composition comprising a dichroic pigment and polymerizable liquid crystal and the film obtained etc. can be enumerated. The film preferably has a protective film on one or both sides. As the protective film, the base material identical with the base material illustrated in the preceding text can be enumerated.

[0276] The film formed by coating the dye having absorption anisotropy is preferably as thin as possible, but if it is too thin, the strength tends to decrease and the processability tends to be poor. The thickness of the film is, for example, 20 μm or less, preferably 5 μm or less, and more preferably 0.5 to 3 μm.

[0277] Specific examples of the film formed by coating a dye having absorption anisotropy include films described in JP-A-2012-33249 and the like.

[0278] The polarizing film may include a transparent protective film. The transparent protective film may be attached to at least one side of the polarizer using an adhesive. As the transparent protective film, the same transparent film as the substrate exemplified above can be preferably used.

[0279] The polarizing plate according to the present embodiment can be obtained by laminating the optical film or laminate according to the above-mentioned embodiment and a polarizing film via an adhesive layer or the like, for example.

[0280] The light transmitted through the polarizing plate according to the present embodiment may be linearly polarized light, circularly polarized light, or elliptically polarized light.

[0281] For the polarizing plate, in the case of linear polarized light, the optical film and the polarizing film according to the above embodiment are preferably stacked in such a manner that the angle formed by the slow axis (optical axis) of the optical film and the absorption axis of the polarizing film is 0±5° or 90±5°. For the polarizing plate, in the case of circularly polarized light, the optical film and the polarizing film according to the above embodiment are preferably stacked in such a manner that the angle formed by the slow axis (optical axis) of the optical film and the absorption axis of the polarizing film is 45±5°.

[0282] The polarizing plate according to the present embodiment may include, for example, a pressure-sensitive adhesive layer (sheet) for bonding the polarizing plate to a display element such as an organic EL, a protective film used to protect the surface of the polarizer or optical film from damage and contamination, and the like.

[0283] [Image display device]

[0284] The image display device involved in this embodiment has the polarizing plate involved in the above embodiment. The so-called image display device is a device having a display element, including a light-emitting element or a light-emitting device as a light source. The image display device can be, for example, a liquid crystal display device, an organic electroluminescent (EL) display device, an inorganic electroluminescent (EL) display device, a touch panel display device, an electron emission display device (such as a field emission display device (FED), a surface field emission display device (SED)), an electronic paper (a display device using electronic ink and an electrophoretic element), a plasma display device, a projection display device (such as a grating light valve (GLV) display device, a display device having a digital micromirror device (DMD)) and a piezoelectric ceramic display.

[0285] The liquid crystal display device includes any display device of a transmissive liquid crystal display device, a semi-transmissive liquid crystal display device, a reflective liquid crystal display device, a direct-view liquid crystal display device, and a projection liquid crystal display device. These display devices can be display devices that display two-dimensional images, or they can be stereoscopic display devices that display three-dimensional images. The polarizing plate involved in this embodiment can be suitably used in an organic electroluminescent (EL) display device and an inorganic electroluminescent (EL) display device, and the optical film involved in this embodiment can be suitably used in a liquid crystal display device and a touch panel display device. These display devices can present good image display characteristics by having the polarizing plate involved in the above-mentioned embodiment with high reliability.

[0286] Example

[0287] Hereinafter, the present disclosure will be described in more detail based on Examples and Comparative Examples, but the present disclosure is not limited to the following Examples. Unless otherwise specified, "%" and "part" in the examples refer to mass % and mass part, respectively.

[0288] [Examples 1 to 10 and Comparative Example 1]

[0289] (Preparation of Photo-Alignment Film-Forming Composition)

[0290] The photo-aligned polymer (weight average molecular weight: 50,000, m:n=50:50) having the structure shown below was produced according to the method described in Japanese Patent Application Publication No. 2021-196514. 2 parts of the photo-aligned polymer and 98 parts of cyclopentanone (solvent) were mixed as components to obtain a mixture. The mixture was stirred at 80° C. for 1 hour to prepare a composition for forming a photo-aligned film.

[0291] Photo-oriented materials:

[0292] [Chemical formula 13]

[0293]

[0294] (Production of polymerizable liquid crystal compound)

[0295] A polymerizable liquid crystal compound (P1) and a polymerizable liquid crystal compound (P2) having the structures shown below were prepared respectively. The polymerizable liquid crystal compound (P1) was prepared in the same manner as described in Japanese Patent Publication No. 2019-003177. The polymerizable liquid crystal compound (P2) was prepared in the same manner as described in Japanese Patent Publication No. 2009-173893.

[0296] Polymerizable liquid crystal compound (P1):

[0297] [Chemical formula 14]

[0298]

[0299] Polymerizable liquid crystal compound (P2):

[0300] [Chemical formula 15]

[0301]

[0302] 1 mg of the polymerizable liquid crystal compound (P1) was dissolved in 10 mL of chloroform to obtain a solution. For the obtained solution, a measurement sample was placed in a measurement cuvette with an optical path length of 1 cm, and the measurement sample was set in an ultraviolet visible spectrophotometer ("UV-2450" manufactured by Shimadzu Corporation) to measure the absorption spectrum. The wavelength of the maximum absorbance was read from the obtained absorption spectrum, and as a result, the maximum absorption wavelength λmax in the range of 300 to 400 nm was 356 nm.

[0303] (Preparation of polymerizable liquid crystal composition)

[0304] A polymerizable liquid crystal compound (P1) and a polymerizable liquid crystal compound (P2) were mixed at a mass ratio (P1:P2) of 90:10 to obtain a mixture. 0.1 parts by mass of a leveling agent "BYK-361N" (manufactured by BM Chemie) and additives A to C were added to 100 parts by mass of the mixture. The amounts of additives A to C added to 100 parts by mass of the mixture were set to the values ​​shown in Table 1. The abbreviations in Table 1 are as follows.

[0305] Compound (A31): The compound represented by the above formula (A31) (CLogP: 9.5155)

[0306] Compound (B31): The compound represented by the above formula (B31) (CLogP: 4.352)

[0307] Compound (B32): Compound represented by the above formula (B32) (CLogP: 8.496)

[0308] Compound (C1): a compound represented by the following formula (C1) (CLogP: 3.8153)

[0309] [Chemical formula 16]

[0310]

[0311] N-methyl-2-pyrrolidone (NMP) was further added to the mixture so that the solid content (polymerizable liquid crystal compounds (P1), (P2), additives A to C, and leveling agent) concentration became 13%. The mixture was stirred at 80°C for 1 hour to prepare a polymerizable liquid crystal composition.

[0312] (Production of Laminated Body)

[0313] As a substrate, a biaxially stretched polyethylene terephthalate (PET) film (Diafoil Mitsubishi Resins Co., Ltd.) was prepared. The above-mentioned photo-alignment film-forming composition was applied to one surface of the substrate using a rod coater. After the obtained coating film was dried at 120°C for 2 minutes, it was cooled to room temperature to form a dry film. Then, using a UV irradiation device (SPOTCURE SP-9, manufactured by USHIO INC.), 100mJ of polarized ultraviolet light (based on 313nm) was irradiated to obtain a photo-alignment film. The film thickness of the photo-alignment film measured using an ellipsometer (Ellipsometer) M-220 manufactured by JASCO Corporation was 100nm.

[0314] The polymerizable liquid crystal composition was applied to the obtained photo-alignment film using a bar coater to form a coating film. The coating film was dried by heating at 120°C for 2 minutes and then cooled to room temperature to obtain a dry film. Next, a high-pressure mercury lamp ("Unicure VB-15201BY-A" manufactured by USHIO INC.) was used to expose the film at an exposure of 500 mJ / cm 2 The dried film was irradiated with ultraviolet light (based on 365 nm) to form a horizontally oriented liquid crystal cured film (optical film). Thus, a laminate formed of a substrate / light-oriented film / horizontally oriented liquid crystal cured film was obtained. The polymerizable liquid crystal compound was cured in a state of being oriented in a horizontal direction relative to the substrate surface. The thickness of the optical film measured using a laser microscope LEXTOLS4100 manufactured by Olympus Corporation was 2.0 μm.

[0315] (Preparation of the first test piece)

[0316] The laminate was cut into 4 cm × 4 cm. The surface of the optical film side of the laminate was subjected to a corona treatment once using a corona treatment device (AGF-B10, manufactured by Kasuga Electric Co., Ltd.) (output power: 0.3 kW, treatment speed: 3 m / min). The laminate and the glass were bonded via a pressure-sensitive adhesive (manufactured by LINTEC, thickness: 25 μm). The laminate was bonded so that the corona-treated surface of the laminate was opposite to the glass. The substrate (PET film) was peeled off from the laminate to obtain the first test piece (layer composition: glass / adhesive / optical film / photo-alignment film).

[0317] (Heat treatment)

[0318] The first test piece was left to stand for 30 minutes in a drying oven set at 100° C. Then, the first test piece was taken out of the oven and left to stand for 1 hour in an environment of 25° C. and 55% humidity.

[0319] (Measurement of In-Plane Phase Difference Value of Optical Film Using First Test Specimen)

[0320] The in-plane phase difference value of the optical film was measured using the first test piece before the heat treatment. In the measurement, KOBRA-WR manufactured by Oji Instruments Co., Ltd. was used. The wavelength of light was set to wavelengths of 448.2nm, 498.6nm, 548.4nm, 587.3nm, 628.7nm and 748.6nm. Based on the measurement results of these wavelengths, the in-plane phase difference value for light with wavelengths of 450nm, 550nm and 630nm was calculated using the Cauchy dispersion formula. The results are shown in Table 2.

[0321] The same operation as the optical film before the heat treatment was performed, and the in-plane phase difference value Re(550) of the optical film was obtained using the first test piece after the heat treatment. The change (ΔRe(550)) of the in-plane phase difference value Re(550) before and after the heat treatment was evaluated according to the following criteria. The results are shown in Table 2.

[0322] (Benchmark)

[0323] A: less than 4nm

[0324] B: 4nm or more and less than 5nm

[0325] C: 5nm or more

[0326] (Manufacturing of polarizing film)

[0327] A polyvinyl alcohol film (average degree of polymerization: about 2400, degree of saponification: 99.9 mol% or more, thickness: 30 μm) was immersed in pure water at 30°C. Next, the polyvinyl alcohol film was immersed in an aqueous solution at 30°C and iodine dyeing was performed (hereinafter also referred to as iodine dyeing step). The aqueous solution used in the iodine dyeing step was a mixture of iodine, potassium iodide and water (the mass ratio of iodine: potassium iodide: water was 0.02:2:100).

[0328] The polyvinyl alcohol film after the iodine dyeing step was immersed in an aqueous solution at 56.5°C to perform a boric acid treatment (hereinafter also referred to as a boric acid treatment step). The aqueous solution used in the boric acid treatment step was a mixture of potassium iodide, boric acid and water (the mass ratio of potassium iodide:boric acid:water was 12:5:100).

[0329] The polyvinyl alcohol film after the boric acid treatment step was washed with pure water at 8°C and dried at 65°C. Thus, a polarizer (thickness after stretching was 12 μm) in which iodine was adsorbed and oriented on the polyvinyl alcohol was obtained. The polyvinyl alcohol film was stretched in the iodine dyeing step and the boric acid treatment step. The total stretching ratio in the stretching was 5.3 times.

[0330] On both sides of the polarizer, saponified triacetyl cellulose films (KC4UYTAC, manufactured by Konica Minolta Co., Ltd., thickness: 40 μm) were respectively attached by a clamping roller via a water-based adhesive. The resulting laminate was dried at 60° C. for 2 minutes while maintaining the tension at 430 N / m. A polarizing film having a polarizer and protective films disposed on both sides of the polarizer was obtained.

[0331] The water-based adhesive used for lamination was prepared by adding 3 parts of carboxyl-modified polyvinyl alcohol (KURARAY POVAL KL318 manufactured by KURARAY CO., LTD.) and 1.5 parts of water-soluble polyamide epoxy resin (Sumirez resin (registered trademark) 650 manufactured by Taoka Chemical Industry Co., Ltd., a 30% solid content aqueous solution) to 100 parts of water.

[0332] The optical properties of the polarizer were measured using a spectrophotometer (V7100, manufactured by JASCO Corporation). The visibility-corrected single transmittance of the polarizer was 42.1%, the visibility-corrected polarization degree was 99.996%, and the single hue was 9.996%. * is -1.1, monomer hue b * is 3.7.

[0333] (Preparation of the Second Test Specimen)

[0334] The first test piece was prepared in the same manner as the preparation of the first test piece. The surface of the photo-alignment film side of the first test piece was subjected to a corona treatment once using a corona treatment device (AGF-B10, manufactured by Kasuga Electric Co., Ltd.) (output power: 0.3 kW, treatment speed: 3 m / min). The polarizing film and the first test piece were bonded together via a pressure-sensitive adhesive (manufactured by LINTEC, thickness: 25 μm). The corona-treated surface of the first test piece was placed opposite to the protective film on one side of the polarizing film, and the angle between the light absorption axis direction of the polarizer and the slow axis direction of the laminate was 45°. Thus, the second test piece having a polarizing plate bonded to glass was obtained (layer structure: glass / adhesive / optical film / photo-alignment film / cellulose triacetate film / polarizer / cellulose triacetate film).

[0335] (Exposure Processing)

[0336] The second test piece was placed in the chamber of a light resistance tester (SANTEST XLS+, manufactured by ATLAS). The second test piece was placed so that the polarizing plate side was on the xenon lamp side. The xenon lamp (illuminance: 267 mW / m 2 ), while the second test piece was left to stand for 300 hours. The second test piece was taken out of the chamber and left to stand for 1 hour in an environment of 25°C and 55% humidity.

[0337] (Measurement of In-Plane Phase Difference Value of Optical Film Using Second Test Specimen)

[0338] The in-plane retardation value of the optical film was measured in the same manner as (Measurement of the in-plane retardation value of the optical film using the first test piece) except that the second test piece before the exposure treatment was used instead of the first test piece.

[0339] Furthermore, the in-plane retardation value of the optical film was measured in the same manner as (Measurement of in-plane retardation value of optical film using first test piece) except that the second test piece after the exposure treatment was used instead of the first test piece.

[0340] The change (ΔRe(450) / Re(550)) of the wavelength dispersion value (Re(450) / Re(550)) of the circularly polarizing plate with glass before and after the exposure treatment was calculated. The change was evaluated according to the following criteria. The results are shown in Table 2.

[0341] (Benchmark)

[0342] A: less than 0.02

[0343] B: 0.02 or more and less than 0.03

[0344] C: 0.03 or more

[0345] The change in Re(550) of the circularly polarizing plate with glass before and after the exposure process (ΔRe(550)) was calculated. The change was evaluated according to the following criteria. The results are shown in Table 2.

[0346] (Benchmark)

[0347] A: less than 4nm

[0348] B: 4nm or more and less than 7nm

[0349] C: 7nm or above

[0350] (Determination of Contents of Compound (A) and Compound (B))

[0351] The contents of compound (A) and compound (B) per unit volume of the optical film were measured. Specifically, about 3 - 4 mg of the optical film was collected by scraping the first test piece from the photo-aligned film side using a spatula. The collected optical film was added to 2 mL of THF (tetrahydrofuran) and left for 24 hours. Thus, an extract in which the target components were extracted into THF was obtained. The extract was subjected to HPLC measurement under the following conditions to perform quantitative analysis of compound (A) and compound (B). Based on the results of the quantitative analysis, the contents of compound (A) and compound (B) per unit volume of the optical film were calculated. The results are shown in Table 1.

[0352] <HPLC Measurement Conditions>

[0353] Measuring device: HPLC LC-10AT (manufactured by Shimadzu Corporation)

[0354] Column: L-column ODS (length: 105 mm, inner diameter: 3 mm, particle size: 3 μm)

[0355] Flow rate: 0.5 mL / minute

[0356] Injection volume: 5 μL

[0357] Detection wavelengths: 254 nm, 350 nm

[0358] Mobile phase A: Water added with 0.1 vol% of TFA (trifluoroacetic acid)

[0359] Mobile phase B: Acetonitrile

[0360] Stabilization time: 15 minutes

[0361] Gradient conditions: 30 minutes with 70% - 100% mobile phase B, then 30 minutes with 100% mobile phase B

[0362] [Table 1]

[0363]

[0364] [Table 2]

[0365]

Claims

1. An optical film comprising a compound (A) having a skeleton represented by the following general formula (A1) as a partial structure, and a compound (B) having a skeleton represented by the following formula (B1) as a partial structure, The content of the compound (A) per unit volume is 1.5 kg / m 3 Above 20kg / m 3 the following, The content of the compound (B) per unit volume is 2.5 kg / m 3 Above 30kg / m 3 the following, [Chemical formula 1] In formula (A1), R 1 represents a hydrogen atom, a hydrocarbon group or a carbonyl group, [Chemical formula 2] 2. The optical film according to claim 1, which satisfies the following formulas (1) and (2): 0.82≤Re(450) / Re(550)≤0.98 (1), 100nm≤Re(550)≤160nm (2), In the formula, Re(450) represents the in-plane phase difference value for light with a wavelength of 450 nm, and Re(550) represents the in-plane phase difference value for light with a wavelength of 550 nm. 3 . The optical film according to claim 2 , which has a thickness of 0.5 μm to 5 μm. The optical film according to claim 1 , comprising a cured product of a polymerizable liquid crystal compound. 5 . A polarizing plate comprising a polarizing film and the optical film according to claim 1 . 6 . An image display device comprising the polarizing plate according to claim 5 .

Citation Information

Patent Citations

  • Compound, optical film, and manufacturing method for optical film

    JP2009173893A

  • Magnetic transfer master substrate, magnetic transfer method using the same and magnetic transfer medium

    JP2012033249A

  • Method for producing polycarbonate, and transparent film

    JP2012214801A

  • Polymerizable liquid crystal composition and retardation plate

    JP2019003177A

  • Polarizing film, polarizing plate, optical laminate, elliptical polarizing plate, organic el display, and flexible image display device

    JP2021196514A